capsule
By selectively selecting nanoparticles and precursors coupled to the second shell component, capsules based on metal oxides or semi-metal oxides are prepared, the stability and safety of active substances in the prior art are solved, low shell permeability and mechanical integrity are achieved, and the shelf life of the product is extended.
Patent Information
- Application Number
- CN202080024410.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-10-10
- Filing Date
- 2020-04-17
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2040-04-17
AI Technical Summary
Existing microencapsulation technologies are difficult to maintain the stability and safety of active substances throughout the supply chain, especially in harsh environments, and traditional polymer capsules have environmental problems.
Capsules based on metal oxide or semi-metal oxide are prepared by selectively selecting nanoparticles and precursors coupled to the second shell component to achieve low shell permeability and mechanical integrity.
It realizes long-term retention and protection of active substances under the premise of environmental and human health and safety, and releases them at the expected time, which helps to extend the shelf life of the product.
Smart Images

Figure BDA0003278857030000421 
Figure BDA0003278857030000431 
Figure BDA0003278857030000432
Abstract
Description
Technical Field
[0001] The present disclosure relates to capsules for the transfer and triggered release of beneficial agents and methods of making the capsules. Background Art
[0002] Microencapsulation is a process in which liquid droplets, solid particles or gases are encapsulated in a solid shell and are generally within a micro-size range. The core material is then mechanically separated from the surrounding environment (Jyothi et al., Journal of Microencapsulation, 2010, 27, 187-197). Microencapsulation technology is receiving attention from various scientific fields and has a wide range of commercial applications in different industries. In general, capsules can achieve one or more of the following: (i) providing the stability of a preparation or material by mechanically separating incompatible components, (ii) protecting the core material from the influence of the surrounding environment, (iii) masking or hiding the undesirable properties of the active ingredient, and (iv) controlling or triggering the release of the active ingredient to a specific time or position. All of these attributes can extend the shelf life of several products and stabilize the active ingredient in the liquid preparation.
[0003] Encapsulation can be found in fields such as pharmaceuticals, personal care, textiles, food, coatings and agriculture. In addition, in practical commercial applications, the main challenge faced by microencapsulation technology is that the encapsulated active substance needs to be completely retained in the capsule throughout the supply chain until the controlled or triggered release of the core material is applied (Thompson et al., Journal of Colloid and Interface Science, 2015, 447, 217-228). There are significantly limited microencapsulation technologies that are safe for the environment and human health, have long-term retention and active protection capabilities, and can meet the needs of today's industry, especially when it involves encapsulation of small molecules.
[0004] In the past few years, consumer product manufacturers have used core-shell encapsulation technology to preserve active substances such as beneficial agents in harsh environments and release them at a desired time, which can be during or after the use of the consumer product. Among the several mechanisms that can be used to release beneficial agents, the mechanism that is usually relied on is mechanical rupture of the capsule shell. Selecting mechanical rupture as a release mechanism poses another challenge to manufacturers because the rupture must occur at a specific desired time, even if the capsule is mechanically stressed before the desired release time.
[0005] Industrial interest in encapsulation technology has led to the development of several polymer capsule chemistries that attempt to meet the requirements of low shell permeability, high deposition, targeted mechanical properties and rupture characteristics. Increased environmental concerns have brought polymer capsules under scrutiny, so manufacturers have begun to investigate sustainable solutions for encapsulating beneficial agents. There is a large amount of literature on sustainable capsules based on metal oxides or semi-metal oxides, primarily silica capsules; however, none of the capsules described in the literature provide the correct balance of low shell permeability, mechanical properties, deposition and rupture characteristics.
[0006] Capsules made with only silane monomers are known in the art. Multiple patent applications and academic publications disclose the use of monomers such as tetramethoxysilane (TMOS) and tetraethoxysilane (TEOS). The advantage of using such monomers is that they react faster than prepolymers made from similar monomers and have therefore been a preferred choice for many years. This rapid reaction time is due to their higher water solubility after partial hydrolysis compared to larger precursors due to the lower molecular weight of the former, which further accelerates the overall hydrolysis kinetics since they are in excess water after being dispersed in the phase. However, these types of disclosures typically use cationic surfactants, such as cetyltrimethylammonium chloride (CTAC) or cetyltrimethylammonium bromide (CTAB), which are presumably used to push the negatively charged hydrolysis intermediate reaction species dispersed in the aqueous phase toward the oil / water interface.
[0007] Without being bound by theory, it is generally the case that partially hydrolyzed monomers in excess water begin to condense and form larger particle sols that are attracted to the oil / water interface. Ultimately, the system is expected to reduce the surface energy of the dispersed particle sols by means of thermodynamic laws, which is conducive to having sols at the oil / water interface, especially when they become larger. The formation of such particle sols will eventually lead to a shell around the oil droplets, and in some cases even to a shell that is strong enough for mechanical self-integrity. However, due to the geometric characteristics of the particle sols (size, fractal dimension, shape, etc.), they cannot form a shell with a dense non-porous network, thereby providing low shell permeability.
[0008] In addition, WO 2011 / 131644 discloses capsules having a semi-metallic organic shell by bonding nanoparticles together using oil-soluble semi-metallic precursors. However, the reference does not disclose a second shell component. In the present invention, it has been found that selectively selecting nanoparticles and precursors coupled to the second shell component can provide capsules with reduced permeability and increased mechanical integrity.
[0009] Without wishing to be bound by theory, applicants have surprisingly found that careful selection of primary shell components, secondary shell components, nanoparticles, core-shell ratios, and shell thickness allow the preparation of metal oxide or semi-metal oxide based capsules that retain their mechanical integrity after air drying on a surface and have low shell permeability in a surfactant based matrix. Both of these properties are desirable results, but are also features of a dense and strong shell with low permeability, which is only possible through a judicious choice of constituent materials and conditions to assemble them. Summary of the invention
[0010] A low toxicity and eco-safe encapsulation technology is needed as an alternative to traditional synthetic chemicals. A method to encapsulate beneficial agents and sustainable materials in a shell by green emulsification technology is desired.
[0011] According to an embodiment, a population of capsules is provided, wherein the capsule may include an oil-based core and a shell surrounding the core. In an embodiment, the oil-based core may include a beneficial agent. In an embodiment, the shell may include a first shell member and a second shell member, wherein the second shell member surrounds the first shell member. In an embodiment, the first shell member may include a condensation layer and a nanoparticle layer, wherein the condensation layer is disposed between the core and the nanoparticle layer. In an embodiment, the condensation layer may include a condensation product of a precursor. In an embodiment, the second shell member may include an inorganic coating, wherein the inorganic coating surrounds the nanoparticle layer. In an embodiment, the precursor comprises at least one compound of formula (I): (M v O z Y n ) w (Formula I), wherein M is one or more of silicon, titanium and aluminum, v is the valence number of M and is 3 or 4, z is 0.5 to 1.6, preferably 0.5 to 1.5, each Y is independently selected from -OH, -OR 2 , halogenated, -NH2, -NHR 2 、-N(R 2 )2 and Where R 2 For C1 to C 20 Alkyl, C1 to C 20 Alkylene, C6 to C 22 aryl, or a 5-12 membered heteroaryl group containing 1 to 3 ring heteroatoms selected from O, N and S, R 3 H, C1 to C 20 Alkyl, C1 to C 20 Alkylene, C6 to C 22 Aryl, or a 5-12 membered heteroaryl group containing 1 to 3 ring heteroatoms selected from O, N and S, n is 0.7 to (v-1), and w is 2 to 2000.
[0012] According to an embodiment, a population of capsules is provided, wherein the capsule may include an aqueous core and a shell surrounding the core. In an embodiment, the aqueous core may include a beneficial agent. In an embodiment, the shell may include a first shell component. In an embodiment, the first shell component may include a condensation layer and a nanoparticle layer. In an embodiment, the condensation layer may include a condensation product of a precursor. In an embodiment, the precursor includes at least one compound of formula (I): (M v O z Y n ) w (Formula I), wherein M is one or more of silicon, titanium and aluminum, v is the valence number of M and is 3 or 4, z is 0.5 to 1.6, preferably 0.5 to 1.5, each Y is independently selected from -OH, -OR 2 , halogenated, -NH2, -NHR 2 、-N(R 2 )2 and Where R 2 For C1 to C 20 Alkyl, C1 to C 20 Alkylene, C6 to C 22 aryl, or a 5-12 membered heteroaryl group containing 1 to 3 ring heteroatoms selected from O, N and S, R 3 H, C1 to C 20 Alkyl, C1 to C 20 Alkylene, C6 to C 22 Aryl, or a 5-12 membered heteroaryl group containing 1 to 3 ring heteroatoms selected from O, N and S, n is 0.7 to (v-1), and w is 2 to 2000.
[0013] According to an embodiment, a population of capsules is provided, wherein the capsule may include an aqueous core and a shell surrounding the core. In an embodiment, the aqueous core may include a beneficial agent. In an embodiment, the shell may include a first shell component. In an embodiment, the first shell component may include a condensation layer and a nanoparticle layer. In an embodiment, the condensation layer may include a condensation product of a precursor. In an embodiment, the precursor includes at least one compound of formula (I) or formula (II): (M v O z Y n ) w (Formula I), wherein M is one or more of silicon, titanium and aluminum, v is the valence number of M and is 3 or 4, z is 0.5 to 1.6, preferably 0.5 to 1.5, each Y is independently selected from -OH, -OR 2 , halogenated, -NH2, -NHR 2 、-N(R 2 )2 and Where R 2 For C1 to C20 Alkyl, C1 to C 20 Alkylene, C6 to C 22 aryl, or a 5-12 membered heteroaryl group containing 1 to 3 ring heteroatoms selected from O, N and S, R 3 H, C1 to C 20 Alkyl, C1 to C 20 Alkylene, C6 to C 22 aryl, or a 5-12 membered heteroaryl containing 1 to 3 ring heteroatoms selected from O, N and S, n is 0.7 to (v-1), and w is 2 to 2000; (M v O z Y n R 1 p ) w (Formula II), wherein M is one or more of silicon, titanium and aluminum, v is the valence number of M and is 3 or 4, z is 0.5 to 1.6, preferably 0.5 to 1.5, each Y is independently selected from -OH, -OR 2 , halogenated, -NH2, -NHR 2 、-N(R 2 )2 and, where R 2 For C1 to C 20 Alkyl, C1 to C 20 Alkylene, C6 to C 22 aryl, or a 5-12 membered heteroaryl group containing 1 to 3 ring heteroatoms selected from O, N and S, R 3 H, C1 to C 20 Alkyl, C1 to C 20 Alkylene, C6 to C 22 aryl, or a 5-12 membered heteroaryl group containing 1 to 3 ring heteroatoms selected from O, N and S, n is 0 to (v-1), each R 1 Independently selected from C1 to C 30 Alkyl, C1 to C 30 Alkylene, C1 to C2 substituted by one or more of halogen, -OCF3, -NO2, -CN, -NC, -OH, -OCN, -NCO, alkoxy, epoxy, amino, mercapto, acryloyl, CO2H, CO2 alkyl, aryl and heteroaryl. 30 Alkyl, and C1 to C2 substituted by one or more of halogen, -OCF3, -NO2, -CN, -NC, -OH, -OCN, -NCO, alkoxy, epoxy, amino, mercapto, acryloyl, CO2H, CO2 alkyl, aryl and heteroaryl. 30 The alkylene group, p is present in an amount up to pmax, and w is 2 to 2000.
[0014] According to an embodiment, a population of capsules is provided, wherein the capsule may include an aqueous core and a shell surrounding the core. In an embodiment, the aqueous core may include a beneficial agent. In an embodiment, the shell may include a first shell component. In an embodiment, the first shell component may include a condensation layer and a nanoparticle layer. In an embodiment, the condensation layer may include a condensation product of a precursor. In an embodiment, the precursor includes at least one compound of formula (II): (M v O z Y n R 1 p ) w (Formula II), wherein M is one or more of silicon, titanium and aluminum, v is the valence number of M and is 3 or 4, z is 0.5 to 1.6, preferably 0.5 to 1.5, each Y is independently selected from -OH, -OR 2 , halogenated, -NH2, -NHR 2 、-N(R 2 )2 and, where R 2 For C1 to C 20 Alkyl, C1 to C 20 Alkylene, C6 to C 22 aryl, or a 5-12 membered heteroaryl group containing 1 to 3 ring heteroatoms selected from O, N and S, R 3 H, C1 to C 20 Alkyl, C1 to C 20 Alkylene, C6 to C 22 aryl, or a 5-12 membered heteroaryl group containing 1 to 3 ring heteroatoms selected from O, N and S, n is 0 to (v-1), each R 1 Independently selected from C1 to C 30 Alkyl, C1 to C 30 Alkylene, C1 to C2 substituted by one or more of halogen, -OCF3, -NO2, -CN, -NC, -OH, -OCN, -NCO, alkoxy, epoxy, amino, mercapto, acryloyl, CO2H, CO2 alkyl, aryl and heteroaryl. 30 Alkyl, and C1 to C2 substituted by one or more of halogen, -OCF3, -NO2, -CN, -NC, -OH, -OCN, -NCO, alkoxy, epoxy, amino, mercapto, acryloyl, CO2H, CO2 alkyl, aryl and heteroaryl. 30 The alkylene group, p is present in an amount up to pmax, and w is 2 to 2000. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Although the specification ends with claims that specifically point out and clearly claim what is considered to be the subject matter of the present disclosure, it is believed that the present disclosure can be more fully understood from the following description in conjunction with the accompanying drawings. Some of these figures may have been simplified by omitting selected elements in order to more clearly show other elements. Such omissions of elements in certain figures do not necessarily indicate the presence or absence of a particular element in any exemplary embodiment unless such is clearly described in the corresponding text description. The drawings are not drawn to scale.
[0016] Figure 1A is a schematic diagram of a method for preparing a capsule according to an embodiment of the present disclosure prepared with a hydrophobic core;
[0017] Figure 2A is a scanning electron microscope image of a capsule of sample Q according to an embodiment of the present disclosure;
[0018] Figure 2B is a scanning electron microscope image of a capsule shell of sample Q according to an embodiment of the present disclosure;
[0019] Figure 3A is a scanning electron microscope image of a capsule of Sample 1 according to an embodiment of the present disclosure, showing an unbroken capsule shell;
[0020] Figure 3B is a scanning electron microscope image of a cross-section of a capsule of Sample 1 according to an embodiment of the present disclosure, showing the capsule shell;
[0021] Figure 4A is a scanning electron microscope image of a capsule of Sample E according to an embodiment of the present disclosure;
[0022] Figure 4B is a scanning electron microscope image of a capsule shell of Sample E according to an embodiment of the present disclosure;
[0023] Figure 5 is an optical microscope image of a capsule of sample C according to an embodiment of the present disclosure;
[0024] Figure 6 is a scanning electron microscope image of a capsule shell of sample Z according to an embodiment of the present disclosure;
[0025] Fig. 7A is a schematic diagram of a process of forming a second shell member according to an embodiment of the present disclosure;
[0026] Figure 7B The capsule of sample G according to the embodiment of the present disclosure is Fig. 7A Scanning electron microscope image after the process shown in;
[0027] Fig. 8Ais a scanning electron microscope image of a capsule of sample H having both a first shell member and a second shell member according to an embodiment of the present disclosure;
[0028] Figure 8B is a scanning electron microscope image of a capsule shell of sample H having both a first shell component and a second shell component according to an embodiment of the present disclosure;
[0029] Fig. 9 is a scanning electron microscope image of a capsule of a comparative example sample W according to an embodiment of the present disclosure;
[0030] Fig.10 is an energy dispersive X-ray spectrum of a capsule of sample K according to an embodiment of the present disclosure;
[0031] Fig.11 is an energy dispersive X-ray spectrum of a capsule of sample AA according to an embodiment of the present disclosure;
[0032] Fig. 12A is an optical microscope image of a capsule of sample N according to an embodiment of the present disclosure prepared using a hydrophilic core;
[0033] Fig. 12B is a scanning electron microscope image of a capsule of sample N according to an embodiment of the present disclosure prepared using a hydrophilic core;
[0034] Fig.13 is a graph of percent tracer loss as measured by a permeability method versus percent organic content in a first shell component according to an embodiment of the present disclosure;
[0035] Fig.14 is a plot of average shell thickness versus average volume weighted diameter of capsules according to embodiments of the present disclosure;
[0036] Fig.15A is a scanning electron microscope image of a capsule shell of sample B according to an embodiment of the present disclosure;
[0037] Fig. 15B is a scanning electron microscope image of a capsule of sample B according to an embodiment of the present disclosure;
[0038] Fig.16 is a scanning electron microscope image of a capsule shell of sample AW according to an embodiment of the present disclosure;
[0039] Fig.17 is a plot of degree of branching versus molecular weight according to embodiments of the present disclosure. DETAILED DESCRIPTION
[0040] According to an embodiment, an inorganic capsule having a core surrounded by a shell is provided. The core may include one or more beneficial agents. In various embodiments, the shell may include a first shell member and an optional second shell member surrounding the first shell member. In an embodiment, the first shell member may include a condensation layer formed by a condensation product of a precursor. As described in detail below, the precursor may include one or more precursor compounds. In an embodiment, the first shell member may include a nanoparticle layer. In an embodiment, the second shell member may include an inorganic material.
[0041] The capsule of the present invention is defined as comprising a substantially inorganic shell comprising a first shell member and a second shell member. By substantially inorganic is meant that the first shell member may contain up to 10 wt%, preferably 9 wt%, preferably 8 wt%, preferably 7 wt%, preferably 6 wt%, preferably 5 wt%, preferably 4 wt%, preferably 3 wt%, preferably 2 wt%, preferably 1 wt% organic content, as defined later in the organic content calculation and later in the description. Although the first shell member can be used to construct a mechanically stable scaffold or skeleton, it can also provide low shell permeability in liquid products containing surfactants (such as laundry detergents, shower gels, cleaning agents, etc.). (See Surfactants in Consumer Products, J. Falbe, Springer-Verlag). The second shell member greatly reduces the shell permeability, which improves the capsule impermeability in a surfactant-based matrix, as determined by a shell permeability test; (as described below).
[0042] In the present invention, capsules can be formed by first blending a hydrophobic material with an inorganic precursor of formula (I) described later (wherein M is preferably silicon). The precursor / oil mixture is then used as a dispersed phase or as a continuous phase in combination with water, wherein in the former case an O / W emulsion is formed, and in the latter case a W / O emulsion is formed once the two phases are mixed and homogenized by methods known to those skilled in the art.
[0043] In the case where M is silicon in the inorganic precursor of formula (I), the silicon dioxide precursor will begin to react with water at the oil / water interface to hydrolyze, to form a partially hydrolyzed precursor with a silanol group. Then, the partially hydrolyzed precursor can react with another hydrolyzed precursor to form a siloxane bond, thereby releasing a water molecule, or react with an unhydrolyzed precursor to form a siloxane bond, thereby releasing an alcohol molecule. The silicon dioxide precursor can also undergo additional hydrolysis before reacting with another substance. In addition, the silicon dioxide precursor can react with the nanoparticles located at the oil / water interface by a similar mechanism involving alcohol or water to release a condensation reaction, which depends on the hydrolysis state of the precursor. All of the above processes are used for anchoring the silicon dioxide precursor at the oil / water interface.
[0044] The inorganic precursors of formula (I) are characterized by various physical properties, namely molecular weight (Mw), degree of branching (DB) and polydispersity index (PDI) of the molecular weight distribution. Mw and DB have been found to be important for obtaining capsules that retain their mechanical integrity after drying on a surface and have low shell permeability in a surfactant-based matrix.
[0045] Without being bound by theory, it is believed that by anchoring the inorganic precursor of formula (I) so neatly to the interface, a low water environment is provided, which has a structural effect on the resulting shell. Due to the limited contact between the reactants (i.e., water and precursors), this low water environment will result in a much slower reaction time than when using monomer precursors or low MW oligomers. In the present invention, we overcome these shortcomings by carefully selecting the type of precursors and nanoparticles used, thereby causing the formation of a dense capsule shell. Without being limited by theory, it is believed that during hydrolysis, the interfacial activity of the inorganic precursor with low MW is not enough to begin to form the first shell component, so most of it is dispersed into the aqueous phase, reducing the final yield of the shell formation. Once the shell begins to form, the inorganic precursor with low MW can still diffuse through the formed shell, thereby further reducing the required yield of the shell. In addition, inorganic precursors with too little branching have fractal dimensions that make them transparent to each other (Applied Catalysis A, Vol. 96, p. 103, 1993), which means that two precursors with low MW and low DB are unlikely to react with each other to form a solid shell, either leaving voids in the shell or causing the precursor to be lost to the aqueous phase. If a higher concentration of inorganic precursor is used to compensate for this loss, the aqueous phase will contain too much inorganic precursor, and eventually the entire system will gel. Finally, inorganic precursors immersed in excess water (i.e., dispersed in water) tend to react faster and lead to the rapid growth of larger polymers and particles. As described above, larger polymers and particles have limited ability to penetrate into the existing network, so the yield of the shell will not be increased or at least a sufficiently dense shell will not be provided.
[0046] Therefore, in order to obtain capsules according to the invention, capsules having a dense and strong shell, characterized by low shell permeability and the ability of mechanical self-integrity in a surfactant-based matrix, the precursor has a degree of branching higher than 0.19, preferably higher than 0.2 and a molecular weight higher than 600 Da, preferably higher than 700 Da, preferably higher than 1000 Da.
[0047] In certain embodiments, a mixture comprising a precursor of formula (I) and a precursor of TBOS can also be used to obtain capsules that provide low shell permeability and good mechanical properties in a surfactant-based matrix. It has been found that when used with a precursor of formula (I), permeability is reduced relative to the use of a precursor of formula (I) alone. This effect is more pronounced for higher molecular weight precursors.
[0048] Without being bound by theory, it is believed that the use of TBOS reduces the porosity of the capsule shell, thereby resulting in a denser shell network. As is known in the art, the larger the size of the alkoxy chain bonded to the silicon atom, the slower the hydrolysis reaction. Therefore, it is believed that when the precursor of formula (I) carries an alkoxy moiety that is shorter than the butoxy moiety of TBOS, the former will start to react first and form an initial shell. TBOS will start to hydrolyze at a later stage and will subsequently react at the only location where water can still be found (i.e. the pores of the shell), thereby ensuring that the overall permeability of the shell is greatly reduced and leads to a reduction in capsule permeability.
[0049] The main function of the second shell component is to reduce the shell permeability. The second shell component can also greatly improve the capsule mechanical properties, such as capsule rupture force and rupture strength. Without being bound by theory, it is believed that the second shell component helps densify the entire shell by depositing the precursor in the holes retained in the first shell component. The second shell component also adds an additional inorganic layer to the surface of the capsule.
[0050] The second shell member comprises an inorganic material selected from SiO2, TiO2, Al2O3, ZrO2, ZnO2, CaCO3, Ca2SiO4, Fe2O3, Fe3O4, clay, gold, silver, iron, nickel and copper, preferably selected from SiO2. In other embodiments, the preferred component is calcium carbonate. Preferably, the second shell member material has the same type of chemical properties as the first shell member to maximize chemical compatibility. Second shell members made of organic materials are known in the prior art, but differ from the inorganic second shell members of the present invention in that second shell members made of organic materials generally do not provide a low permeability capsule shell or a mechanically improved capsule.
[0051] The improved capsule mechanical properties provided by the use of a second shell component, as disclosed in the present invention, can only be achieved in combination with a unique first shell component. For example, capsules made from tetraethoxysilane (TEOS) and commercial polyethoxysilanes (e.g., Evonik Dynasylan 40) do not provide satisfactory mechanical properties when further combined with an inorganic second shell component. As disclosed in the present invention, the unique combination of the first shell component and the second shell component provides both low shell permeability and mechanical robustness in a surfactant-based matrix.
[0052] Without being bound by theory, it is believed that the second shell component as disclosed in the present invention has the unique property of being deposited into the micropores of the first shell component and covering a large portion of the final capsule surface, thereby providing improved mechanical robustness of the capsule. The filling of the micropores reduces the formation of microcracks when the capsule is under high agitation stress and when the shell is drying. A common solution to capsule shell microcrack formation may be to use unstable spacers in the capsule shell network, but this requires the introduction of organic materials, and these organic materials generally greatly increase the shell permeability of surfactant-based matrices (such as laundry detergents).
[0053] In an embodiment, the first shell member may include a condensation layer and a nanoparticle layer, wherein the condensation layer is disposed between the core and the nanoparticle layer. In an embodiment, the first shell member may include metal oxides and / or semi-metal oxides. In an embodiment, the first shell member may include metal, mineral, metal oxide and / or semi-metal oxide nanoparticles. In an embodiment, the nanoparticles may be one or more of SiO2, TiO2, Al2O3, ZrO2, ZnO2, Fe2O3, Fe3O4, CaCO3, clay, silver, gold and copper. The condensation layer and the nanoparticle layer may have the same or different materials when both are present. In an embodiment, the first shell member is entirely or substantially entirely SiO2.
[0054] In an embodiment, the first shell member is completely inorganic. In an embodiment, the first shell member may include up to 5% by weight of first shell member organic material. For example, the organic material may be present in the precursor and / or nanoparticles and / or added as a separate component. In an embodiment, the organic material may be from unreacted monomers or byproducts of polymerization. In an embodiment, the nanoparticles may include a surface modification containing an organic material. In an embodiment, the organic material may be added to the first shell member.
[0055] In an embodiment, the capsule may further include a second shell member, wherein the second shell member surrounds the first shell member. In an embodiment, the second shell member comprises one or more of a metal oxide, a semi-metal oxide, a mineral, and a metal. In an embodiment, the second shell member may comprise one or more of SiO2, TiO2, Al2O3, ZrO2, ZnO2, CaCO3, Ca2SiO4, Fe2O3, Fe3O4, clay, gold, silver, iron, nickel, and copper. In an embodiment, the second shell member is entirely or substantially entirely SiO2.
[0056] In embodiments, the shell includes only the first shell member. In other embodiments, the shell includes both the first shell member and the second shell member. In embodiments, the first shell member and the second shell member are entirely or substantially entirely SiO2. It is also contemplated herein that the shell may include additional shell members. In various embodiments, the core may be an oil-based core. In other embodiments, the core may be a water-based core.
[0057] The capsules of the present invention include certain physical parameters, such as shell thickness and capsule diameter. The combination and existence of unique limitations of capsule size, shell thickness and effective core / shell ratio that lead to low permeability of the shell are the cornerstones of the present invention. Not only are each of these values important, but their ratio (i.e., core / shell ratio) is also important. For example, a shell that is too thin compared to the overall size of the capsule tends to lack self-integrity and collapses once deposited on the surface and dried. On the other hand, a very thick shell tends to have an increased shell permeability in a surfactant-based matrix compared to the diameter of the capsule. Although it may be thought that a thick shell would lead to low shell permeability (because this parameter affects the overall diffusion path through the shell), it has been surprisingly found that capsules with shells having a thickness above a certain threshold have higher shell permeability. This finding is contrary to the findings known in the prior art, in which it is believed that increased shell thickness provides low shell permeability; the capsules of the present invention demonstrate that the teachings of the prior art are not always applicable in terms of shell thickness and shell permeability.
[0058] Without being bound by theory, it is believed that there are two options for increasing the shell thickness of the capsule: the first option is that for the same amount of precursor, trying to obtain a thicker shell may result in a porous shell and therefore a capsule with low shell permeability in a surfactant-based matrix; the second option is to increase the amount of precursor in the core before the emulsification step. In this second case, the thickness of the first shell component will increase as the reaction proceeds. However, at a certain point, due to the progress of the reaction, the shell becomes so dense that the remaining precursor cannot be hydrolyzed in contact with the water phase, thereby further limiting the increase in shell thickness. This thickness is an upper threshold. Therefore, a capsule with a thick first shell component is obtained, in which the porous shell density is not sufficient to prevent further reaction with external water. It has been found that the capsule of the present invention cannot increase the thickness of the first shell component above the upper threshold, and it is not permeable. However, the upper thickness threshold increases with the increase of the capsule diameter.
[0059] In order for capsules containing core materials to be functional and cost-effective in consumer product applications such as liquid detergents or liquid fabric softeners, they should: i) resist diffusion of the core during the shelf life of the liquid product; ii) have the ability to deposit on a target surface during application (e.g., a washing machine cycle); and iii) be able to release the core material by mechanical shell rupture at the appropriate time and place to provide the desired benefit to the end consumer.
[0060] It is known that the size of the capsules has a critical impact on the efficiency of the capture and deposition of the capsules on a target substrate such as fabric or hair. A certain minimum capsule size is required to maximize their capture when passing through a fabric web or hair strand. However, when the capsules are too large, they can be noticed by an unpleasant grainy feel or simply by the naked eye.
[0061] Shell thickness is usually selected as a compromise between providing low shell permeability and mechanical strength. In fact, thin shells can cause poor barrier properties to a certain extent to which small volatile molecules are diffused through capsule shells (such as flavor raw materials). However, thick shells provide good barrier properties, but the cost is that the effective load of core material is lower, which greatly increases the encapsulation cost of delivering a certain amount of core material compared to thinner shells. This is especially a problem for the inorganic shells obtained by sol-gel precursors, because those inorganic shells can experience significant weight loss during the hydrolysis reaction. For example, the shell directly obtained from tetraethoxysilane (TEOS) precursors or by polyalkoxysilane (PAOS) oligomers as intermediate reactants will lose 72% of initial TEOS weight by the hydrolysis of hydrolyzable ethoxy moieties. In order to overcome these inherent weight losses, the amount of precursor must be increased by more than 3 times to achieve target shell thickness, which inevitably increases the cost of required raw materials.
[0062] The shell formation mechanism of the present invention can be described as "bricks and mortar". More specifically, the first shell component composed of high molecular weight polyalkoxysilane (PAOS) compounds and optional nanoparticles acts as a "brick", providing structural integrity and mechanical resistance to the capsule shell. The second shell component composed of low molecular weight compounds will diffuse in the void spaces between the bricks, acting as a mortar to further increase the mechanical strength of the shell and significantly reduce the shell permeability.
[0063] In an embodiment, the capsule shell advantageously has low permeability, which advantageously allows the encapsulated beneficial agent to diffuse slowly when incorporated into a formulated product. In an embodiment, the capsule may have improved storage stability, such as exhibiting reduced shell permeability and the encapsulated beneficial agent diffusing slowly over storage time. Without being bound by theory, it is believed that the capsule shell according to an embodiment of the present disclosure has low porosity and high density, thereby enhancing the stability of the capsule compared to conventional inorganic capsules. In addition, without being bound by theory, it is believed that the improved shell construction allows the target rupture strength to be achieved, thereby allowing the final rupture at the target pressure during use. That is, despite the increased density and structural stability, the capsule is still able to function as expected during use and rupture at the desired pressure and expected pressure.
[0064] Permeability as measured by the Permeability Test Method described below is related to the porosity of the capsule shell. In embodiments, a capsule or a population of capsules has a permeability of about 0.01% to about 80%, about 0.01% to about 70%, about 0.01% to about 60%, about 0.01% to about 50%, about 0.01% to about 40%, about 0.01% to about 30%, or about 0.01% to about 20%, as measured by the Permeability Test Method. For example, the permeability can be about 0.01%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, or 80%.
[0065] According to embodiments, a capsule or population of capsules may have an average volume weighted capsule diameter of at least 10 microns, an average shell thickness of at least 170 nm, and a coefficient of variation in capsule diameter of less than or equal to 40%.In embodiments, the capsule has a liquid core at room temperature.
[0066] In variations of the embodiments described herein, the capsule may have an average shell thickness of about 10 nm to about 10,000 nm, about 10 nm to about 1000 nm, about 170 nm to 10,000 nm, about 170 nm to about 1000 nm, about 300 nm to about 1000 nm. In embodiments, the shell may have a thickness of about 50 nm to about 1000 nm, about 10 nm to about 200 nm, about 100 nm to about 1000 nm, about 200 nm to about 1000 nm, about 300 nm to about 1000 nm, about 300 nm to about 800 nm, about 300 to about 700 nm, about 300 nm to about 500 nm, or about 300 nm to about 400 nm. For example, the shell thickness can be about 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 125 nm, 150 nm, 175 nm, 200 nm, 225 nm, 250 nm, 275 nm, 300 nm, 325 nm, 350 nm, 375 nm, 400 nm, 425 nm, 450 nm, 475 nm, 500 nm, 525 nm, 550 nm, 575 nm, nm, 600nm, 625nm, 650nm, 675nm, 700nm, 725nm, 750nm, 775nm, 800nm, 825nm, 850nm, 875nm, 900nm, 925n m, 950nm, 975nm, 1000nm, 2000nm, 3000nm, 4000nm, 5000nm, 6000nm, 7000nm, 8000nm, 9000nm or 10,000nm.
[0067] In various embodiments described herein, the capsule can have an average volume weighted capsule diameter of about 0.1 micron to about 300 microns, about 0.1 micron to about 100 microns, about 10 microns to about 200 microns, about 10 microns to about 100 microns, about 10 microns to about 75 microns, about 50 microns to about 100 microns, or about 10 microns to about 50 microns. Other suitable average volume weighted capsule diameters are about 0.1 micron, 0.5 micron, 1 micron, 5 microns, 10 microns, 15 microns, 20 microns, 25 microns, 30 microns, 35 microns, 40 microns, 45 microns, 50 microns, 55 microns, 60 microns, 65 microns, 70 microns, 75 microns, 80 microns, 85 microns, 90 microns, 95 microns, 100 microns, 125 microns, 150 microns, 175 microns, 200 microns, 225 microns, 250 microns, 275 microns, or 300 microns.
[0068] In various embodiments, a capsule population with a large average diameter may be provided. For example, in various embodiments, capsules with an average diameter of 10 μm or greater or 12 μm or greater may be provided. In various embodiments, a capsule population may have a capsule population average diameter greater than 10 μm. In various embodiments, 60%, 70%, 80%, 90% and up to 100% of the capsules may be provided with a capsule population with a diameter greater than 10 μm. Large capsule diameters may be advantageous for including more beneficial agents, thereby allowing the concentration of beneficial agents to be increased in the formulated product without significant capsule concentration. It has been advantageously found that large capsules may be provided according to the embodiments herein without sacrificing the stability of the capsule as a whole and / or while maintaining good burst strength.
[0069] In embodiments, the capsules may have an average shell thickness divided by the average diameter greater than about 0.1%. In embodiments, the capsules may have an average shell thickness divided by the average diameter greater than about 0.2%, or greater than about 0.5%, or greater than about 1%. For example, the capsules may have an average shell thickness divided by the average diameter greater than about 0.2% to about 10%, or 0.2% to about 9%, or about 0.2% to about 7.8%, or about 0.2% to about 6%, or about 0.2% to about 5.6%, or about 0.5% to about 5.6%.
[0070] It has been surprisingly found that, in addition to the inorganic shell, the volumetric core-shell ratio plays an important role in ensuring the physical integrity of the capsule. Shells that are too thin compared to the overall size of the capsule (core:shell ratio>98:02) tend to lack self-integrity and collapse once deposited and dried on the surface. On the other hand, very thick shells tend to have higher shell permeability in surfactant-rich matrices relative to the capsule diameter (core:shell ratio<80:20). Although one might intuitively think that thick shells would lead to lower shell permeability (because this parameter affects the average diffusion path of the active substance through the shell), it has been surprisingly found that capsules of the present invention with shells having a thickness above a threshold have higher shell permeability. This upper threshold depends on the capsule diameter.
[0071] By selecting the composition of the shell precursor and the core material, an effective and creative core:shell ratio is obtained. When the core:shell ratio is too low, a large amount of the first shell material usually leads to core gelation, which adversely affects the migration of the shell material at the oil / water interface by destroying the brick and mortar mechanism. When the core-shell ratio is too large, the mechanical strength provided by the thin shell is not enough to maintain the core weight when dried on the substrate.
[0072] In an embodiment, the capsule may have an average effective volume core-shell ratio of about 60:40 to about 99:1, about 70:30 to about 99:1, about 80:20 to about 99:1, 60:40 to about 98:2, about 70:30 to about 98:2, about 80:20 to about 98:2, about 70:30 to about 96:4, about 80:20 to about 96:4, about 90:10 to about 96:4. For example, the average effective volume core-shell ratio may be about 60:40, 65:35, 70:30, 75:25, 80:20, 85:15, 90:10, 95:5, 98:2, or 99:1, and any combination thereof.
[0073] In an embodiment, the capsule may have an average effective volume core-shell ratio of about 99:1 to about 50:50, with an average volume weighted capsule diameter of about 0.1 μm to about 200 μm and an average shell thickness of about 10 nm to about 10,000 nm. In an embodiment, the capsule may have an average effective volume core-shell ratio of about 99:1 to about 50:50, with an average volume weighted capsule diameter of about 10 μm to about 200 μm and an average shell thickness of about 170 nm to about 10,000 nm. In an embodiment, the capsule may have an average effective volume core-shell ratio of about 98:2 to about 70:30, with an average volume weighted capsule diameter of about 10 μm to about 100 μm and an average shell thickness of about 300 nm to about 1000 nm.
[0074] In an embodiment, the capsule may have a core-shell weight ratio of about 60 to 40 to about 99 to 1, about 70 to 30, about 80 to 20, about 70 to 30 to about 96 to 4, about 80 to 20 to about 96 to 4, about 90 to 10 to about 96 to 4. For example, the core-shell weight ratio may be about 60:40, 65:35, 70:30, 75:25, 80:20, 85:15, 90:10, 95:5, 98:2, or 99:1.
[0075] In embodiments, methods according to embodiments of the present disclosure can produce capsules with low capsule diameter coefficient of variation. In embodiments, a capsule population can have a capsule diameter coefficient of variation of 50% or less, 40% or less, 30% or less, or 20% or less. For example, the capsule diameter coefficient of variation can be less than or equal to 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49% or 50%. Control of capsule size distribution can beneficially allow a population to have improved and more uniform burst strength. Additionally, in embodiments, the burst strength can be more effectively tuned with variations in parameters such as shell thickness, core material, since the effect of capsule size is limited in the population due to the narrow distribution of sizes.
[0076] In embodiments, the capsules herein may have an average burst strength of at least 0.1 MPa, or at least 0.25 MPa, or from about 0.1 MPa to about 10 MPa, or from about 0.25 MPa to about 10 MPa, or from about 0.1 MPa to about 5 MPa, or from about 0.25 MPa to about 5 MPa, or from about 0.1 MPa to about 3 MPa, or from about 0.25 MPa to about 3 MPa. For example, the average rupture strength may be about 0.1 MPa, 0.2 MPa, 0.25 MPa, 0.3 MPa, 0.4 MPa, 0.5 MPa, 0.6 MPa, 0.7 MPa, 0.8 MPa, 0.9 MPa, 1 MPa, 1.1 MPa, 1.2 MPa, 1.3 MPa, 1.4 MPa, 1.5 MPa, 1.6 MPa, 1.7 MPa, 1.8 MPa, 1.9 MPa, 2 MPa, 3 MPa, 4 MPa, or 5 MPa. Completely inorganic capsules, such as certain embodiments herein, traditionally have poor rupture strength, and herein, the rupture strength of the capsules may be greater than 0.25 MPa, thereby providing improved stability and triggered release of the beneficial agent at a specified amount of rupture stress.
[0077] In various embodiments, the capsules may have mechanical properties defined according to a parameter of nominal wall tension, which is the tension or stretch of the capsule wall at rupture. The nominal wall tension value is independent of capsule size (Wang et al., "Modelling the mechanical properties of single suspension-cultured tomato cells", Annals of Botany, Vol. 93, No. 4, pp. 443-453, 2004). Due to such unique properties, the nominal wall tension can be used to compare the mechanical properties of capsules of different average sizes. Nominal wall tension T R The calculation was performed using the method described in “Liu, M. (2010). Understanding the mechanical strength of microcapsules and their adhesion on fabric surfaces. Birmingham, United Kingdom: University of Birmingham (Doctoralthesis)”.
[0078] According to embodiments, the capsules may have an average nominal wall tension of at least 0.1 N / m, or at least 0.25 N / m, or from about 0.1 N / m to about 20 N / m, or from about 0.25 N / m to about 20 N / m, or from about 0.5 N / m to about 20 N / m, or from about 0.5 N / m to about 15 N / m, or from about 1 N / m to about 15 N / m. For example, the average nominal wall tension can be about 0.1 N / m, 0.2 N / m, 0.3 N / m, 0.4 N / m, 0.5 N / m, 0.6 N / m, 0.7 N / m, 0.8 N / m, 0.9 N / m, 1 N / m, 1.1 N / m, 1.2 N / m, 1.3 N / m, 1.4 N / m, 1.5 N / m, 1.6 N / m, 1.7 N / m, 1.8 N / m, 1.9 N / m, 2 N / m, 3 N / m, 4 N / m, 5 N / m, 6 N / m, 7 N / m, 8 N / m, 9 N / m, 10 N / m, 11 N / m, 12 N / m, 13 N / m, 14 m.N / m or 15 m.N / m.
[0079] According to an embodiment, the capsules may be prepared by employing a Pickering emulsifier.
[0080] The capsules of the present invention comprise a shell surrounding a core, wherein the shell comprises a first shell component and an optional second shell component. In some embodiments, the first shell component comprises nanoparticles, which are preferably of the same chemical type as the first shell component formed by hydrolysis and condensation reaction of the precursor of formula (I).
[0081] Although the capsules of the present invention can be prepared without the use of nanoparticles due to the good interfacial activity of the precursors of formula (I), the use of nanoparticles affects the shell formation mechanism in a way that leads to a denser layer of the condensed precursors of formula (I), for reasons detailed below.
[0082] In embodiments, the method of preparing an oil-based core capsule may include using hydrophilic nanoparticles as a Pickering emulsifier. According to the literature (Langmuir 2013, 29, 49, 15457-15462), using nanoparticles that do not strongly adhere to the emulsion interface (in this case, hydrophilic nanoparticles) can provide a fine-tuned emulsion process, wherein the separation energy required to remove the nanoparticles from the interface is minimal. Without being bound by theory, it is believed that this allows a thicker condensation layer to form, and the nanoparticles move from the water-oil interface to the water-hydrolysis precursor interface ( Figure 1A ), the water-hydrolyzed precursor interface is thermodynamically more favorable because the precursor begins to hydrolyze and becomes less hydrophobic. The hydrophilic nanoparticles preferentially adhere to the newly formed water-hydrophilic precursor interface. The hydrolyzed precursor then condenses to form a solid first shell component.
[0083] In an embodiment, a capsule having an oil-based core can be prepared by blending an oil phase with an aqueous phase and emulsifying the blend under conditions sufficient to disperse the oil phase droplets in the aqueous phase. The oil phase may include an oil-based core conditioning agent and / or an oil-soluble beneficial agent and a precursor. The aqueous phase may include water and nanoparticles. In an embodiment, the aqueous phase may also include an acid. After emulsification, nanoparticles from the aqueous phase self-assemble around the oil droplets and are intercalated at the interface between the continuous aqueous phase and the dispersed oil phase, thereby stabilizing the emulsion and defining a nanoparticle layer. In addition, the precursor present in the oil droplets hydrolyzes and condenses at the interface between the continuous aqueous phase and the dispersed oil phase between the nanoparticle layer and the oil droplets. The method then also includes curing the emulsion under conditions that further cure the hydrolyzed and condensed precursors, thereby forming a condensation layer. The nanoparticle layer and the condensation layer thus form the first shell component of the shell. Without being bound by theory, it is believed that covalent bonds are formed between the condensation precursors and the nanoparticles.
[0084] In an embodiment, a capsule having a water-based core can be prepared by blending an aqueous phase with an oil phase and emulsifying the blend under conditions sufficient to disperse droplets of the aqueous phase in the oil phase. The aqueous phase may contain a water-based and / or water-soluble beneficial agent. The oil phase may contain a precursor. One or both of the aqueous phase and the oil phase may contain nanoparticles. After emulsification, the nanoparticles self-assemble around the water droplets and are intercalated at the interface between the dispersed aqueous phase and the continuous oil phase, thereby defining a nanoparticle layer. In addition, the precursor present in the continuous oil phase hydrolyzes and condenses at the interface between the continuous oil phase and the dispersed aqueous phase. The method then further comprises curing the emulsion under conditions of curing the hydrolyzed and condensed precursors, thereby forming a condensation layer. The nanoparticle layer and the condensation layer thus form a first shell component of the shell. Without being bound by theory, it is believed that covalent bonds are formed between the condensation precursors and the nanoparticles.
[0085] In an embodiment, the method (whether comprising a water-based core or an oil-based core) may further comprise forming a second shell member surrounding the first shell member by admixing the capsule with a solution having a second shell member precursor under conditions sufficient to form the second shell member on top of the first shell member of the capsule and in close connection therewith. The solution having the second shell member precursor may comprise a water-soluble or oil-soluble precursor. As described above, the second shell member may be inorganic.
[0086] In an embodiment, the method may further include washing and drying the capsule using any suitable method after the process of forming the second shell component. For example, centrifugation may be used in the washing step. Drying methods are known in the art. An example of drying may be spray drying.
[0087] In embodiments, the method of preparing an oil-based core capsule may include using hydrophilic nanoparticles as a Pickering emulsifier. Without being bound by theory, it is believed that using hydrophilic nanoparticles can provide a fine-tuned emulsion process, wherein the nanoparticles do not adhere strongly to the emulsion interface, and thus the separation energy to remove the nanoparticles from the interface is lower. Without being bound by theory, it is believed that this allows a thicker condensation layer to form and the nanoparticles to move from the water-oil interface to the water-precursor interface ( Figure 1A ), the second interface is thermodynamically more favorable because the precursor begins to hydrolyze and becomes less hydrophobic. The hydrophilic nanoparticles preferentially adhere to the newly formed water-hydrophilic precursor interface. The hydrolyzed precursor then condenses to form a solid first shell component.
[0088] In an embodiment, the result of the method herein is a capsule containing a slurry. In an embodiment, the slurry can be formulated into a product, such as a consumer product. In addition to the slurry, the formulated product may also include one or more processing aids. In an embodiment, the processing aid may include one or more of water, aggregation inhibitors such as divalent salts and particle suspension polymers. In an embodiment, the aggregation inhibitor may include salts that can have a charge shielding effect around the capsule, such as magnesium chloride, calcium chloride, magnesium bromide and magnesium sulfate. In an embodiment, the formulated product may also include one or more of the following: xanthan gum, carrageenan, guar gum, shellac, alginate, chitosan; cellulosic materials such as carboxymethyl cellulose, hydroxypropyl methylcellulose, cationic cellulose materials; polyacrylic acid; polyvinyl alcohol; hydrogenated castor oil; and distearate ethylene glycol. In an embodiment, the formulated product may include one or more carriers. In an embodiment, the carrier may be one or more polar solvents, including but not limited to water, ethylene glycol, propylene glycol, polyethylene glycol and glycerol; and non-polar solvents, including but not limited to mineral oil, fragrance raw materials, silicone oil and hydrocarbon paraffin oil. In embodiments, the formulated product may include one or more of: silicon dioxide, citric acid, sodium carbonate, sodium sulfate, sodium chloride, and a binder such as sodium silicate, modified cellulose, polyethylene glycol, polyacrylate, polyacrylic acid, and zeolite.
[0089] The capsules of the present invention can be formed by polyalkoxysilane (PAOS) or polyalkoxysilane with non-hydrolyzable parts. Those later PAOS produce capsules with residual organic parts in the shell. It has been found that capsules with residual organic parts in the shell show significantly higher shell permeability than capsules without residual organic parts. Adding the second shell component formation step reduces the shell permeability of the capsule, thereby allowing a certain amount of organic parts to enter the first shell component without increasing excessive shell permeability. The main purpose of PAOS is to prepare capsules that do not collapse and have good mechanical properties while also providing low shell permeability. In addition, comparative tests as shown below show that when PAOS is used instead of organosilane to prepare capsules, shell permeability is reduced.
[0090] In some embodiments, the capsule comprises only a first shell member comprising a condensation product of a precursor of formula (I). These capsules can provide the same or similar benefits as those of the present invention comprising a first shell member and a second shell member having low shell permeability in a surfactant-based matrix and the ability to maintain its integrity when dried on a surface. However, when a first shell member and a second shell member are included, the shell permeability is greatly reduced, which is a preferred embodiment of the present invention.
[0091] In certain embodiments, the capsule comprises a first shell component comprising a condensation product of a precursor (ie, an organosilane) of formula (II), or a mixture of formula (I) or (II) and a monomer having one, two, or three carbon-silicon bonds.
[0092] Furthermore, when the capsule comprises both a first shell component and a second shell component, the shell permeability in the surfactant-based matrix is greatly reduced when compared to a capsule lacking the second shell component, wherein the first shell component comprises a condensation product of a precursor of formula (II) or a mixture of a precursor of formula (I) or (II) and a monomer having one, two or three carbon-silicon bonds.
[0093] Thus, while capsules comprising a first shell member and a second shell member, wherein the first shell member comprises a condensation product of a precursor of formula (I) is a preferred embodiment, it has been found that the first shell member can tolerate a portion of the condensation product of a precursor of formula (II), or a mixture of a precursor of formula (I) or (II) with a monomer having one, two or three silicon-carbon bonds, without completely losing the permeation resistance of the surfactant-based matrix in the resulting capsule.
[0094] The portion of the condensation product of the precursor of formula (II) is defined as resulting in a total first shell composition comprising less than 10 wt%, preferably less than 9 wt%, preferably less than 8 wt%, preferably less than 7 wt%, preferably less than 6 wt%, preferably less than 5 wt%, preferably less than 4 wt%, preferably less than 3 wt%, preferably less than 2 wt%, preferably less than 1 wt% organic content as defined in the Organic Content Calculation section.
[0095] Without wishing to be bound by theory, it is believed that the organic compound can act as a spacer within the shell, thereby reducing the crosslink density of the first shell component, and the amount of the spacer is too large to provide significant porosity. Therefore, a first shell component with a sufficiently low level of organic compound can result in higher shell permeability in a surfactant-based matrix while still having sufficient self-integrity when dried on the surface.
[0096] As previously described, while in certain embodiments, the first shell component can serve as a scaffold or skeleton of the capsule to provide mechanical resistance while still providing reduced shell permeability in surfactant-based matrices, the inclusion of a second shell component greatly reduces shell permeability in surfactant-based matrices. In embodiments, the precursor comprises at least one compound of formula (I) and / or at least one compound of formula (II) in combination with one or more of tetraethoxysilane (TEOS), tetramethoxysilane (TMOS), tetrabutoxysilane (TBOS), triethoxymethylsilane (TEMS), diethoxy-dimethylsilane (DEDMS), trimethylethoxysilane (TMES), and tetraacetoxysilane (TAcS).
[0097] In embodiments, emulsified dispersed phase and continuous phase may include one or more of high shear homogenization process, microfluidization process and ultrasonic process. In embodiments, emulsified dispersed phase and continuous phase may include high shear homogenization process. In embodiments, high shear homogenization process may include one or more mixers, such as ultraturrax mixer or vortex mixer. In embodiments, mixer may have a speed of 100rpm to 20,000rpm, or 500rpm to 15,000rpm, or 1000rpm to 10,000rpm, or 2000rpm to 10,000rpm. For example, mixer may have a speed of 1000rpm, 1500rpm, 2000rpm, 2500rpm, 3000rpm, 3500rpm, 4000rpm, 4500rpm, 5000rpm, 6000rpm, 7000rpm, 8000rpm, 9000rpm or 10,000rpm.
[0098] In an embodiment, the dispersed phase and the continuous phase can be emulsified for about 1 minute to about 2 hours, or about 1 minute to about 30 minutes, or about 1 minute to about 10 minutes. For example, the emulsification can be 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes or 10 minutes.
[0099] In embodiments, an emulsion may be formed that is substantially free of surfactant. In embodiments, an emulsion that is "substantially free" of surfactant comprises surfactant in an amount of 0.001% w / w or less.
[0100] In an embodiment, a curing process may be used to cure the shell. In an embodiment, the curing process may cause condensation of the precursor. In an embodiment, the curing process may be completed at room temperature or above room temperature. In an embodiment, the curing process may be completed at a temperature above 30°C. For example, the curing process may be completed at 30°C to 150°C, 40°C to 120°C, 50°C to 100°C, 60°C to 100°C, 70°C to 100°C, or 30°C, 40°C, 50°C, 60°C, 70°C, 75°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, or 150°C.
[0101] In embodiments, curing process can be completed in any suitable time period, so that the capsule shell can be strengthened by the condensation of precursor material. In embodiments, curing process can be completed in 1 minute to 45 days or 1 minute to 10 days or 1 minute to 5 days or 1 minute to 24 hours time period. For example, curing process can be completed in 1 minute, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 12 hours, 24 hours, 48 hours, 72 hours, 96 hours, 5 days, 6 days, 7 days, 8 days, 9 days, 10 days, 15 days, 20 days, 21 days, 25 days, 30 days, 35 days, 40 days or 45 days. In the method described herein, it is also possible to imagine longer curing time.
[0102] First shell component
[0103] In an embodiment, the first shell member may include a condensation layer. The condensation layer may be a condensation product of one or more precursors. The one or more precursors may have formula (I):
[0104] (M v O z Y n ) w (Formula I),
[0105] wherein M is one or more of silicon, titanium and aluminum, v is the valence number of M and is 3 or 4, z is 0.5 to 1.6, preferably 0.5 to 1.5, each Y is independently selected from -OH, -OR 2 , -NH2, -NHR 2 、-N(R 2 )2. Where R 2 For C1 to C 20 Alkyl, C1 to C 20 Alkylene, C6 to C 22 aryl, or a 5-12 membered heteroaryl group containing 1 to 3 ring heteroatoms selected from O, N and S, R 3 H, C1 to C 20 Alkyl, C1 to C 20 Alkylene, C6 to C 22 Aryl, or a 5-12 membered heteroaryl group containing 1 to 3 ring heteroatoms selected from O, N and S, n is 0.7 to (v-1), and w is 2 to 2000.
[0106] In embodiments, one or more precursors may have formula (I), wherein M is silicon. In embodiments, Y is -OR 2 In an embodiment, n is 1 to 3. In an embodiment, Y is -OR 2and n is 1 to 3. In an embodiment, n is at least 2, one or more of Y is -OR 2 , and one or more of Y is -OH. In an embodiment, one or more of Y is
[0107] In an embodiment, R 2 For C1 to C 20 In an embodiment, R 2 C6 to C 22 In an embodiment, R 2 is one or more of C1 alkyl, C2 alkyl, C3 alkyl, C4 alkyl, C5 alkyl, C6 alkyl, C7 alkyl and C8 alkyl. 2 is a C1 alkyl group. 2 is a C2 alkyl group. 2 is a C3 alkyl group. 2 It is a C4 alkyl group.
[0108] In embodiments, z is from 0.5 to 1.3, or from 0.5 to 1.1, from 0.5 to 0.9, or from 0.7 to 1.5, or from 0.9 to 1.3, or from 0.7 to 1.3.
[0109] In an embodiment, M is silicon, v is 4, each Y is -OR 2 , n is 2 and / or 3, and each R 2 It is a C2 alkyl group.
[0110] In embodiments, the precursor may comprise polyalkoxysilane (PAOS).In some embodiments, the precursor may comprise polyalkoxysilane (PAOS) synthesized by a hydrolysis process.
[0111] In embodiments, the precursor may alternatively or additionally comprise one or more of compounds of formula (II):
[0112] (M v O z Y n R 1 p ) w (Formula II),
[0113] wherein M is one or more of silicon, titanium and aluminum, v is the valence number of M and is 3 or 4, z is 0.5 to 1.6, preferably 0.5 to 1.5, each Y is independently selected from -OH, -OR 2 , -NH2, -NHR 2 、-N(R 2 )2. Where R 2 Select from C1 to C 20 Alkyl, C1 to C 20 Alkylene, C6 to C 22 aryl, or a 5-12 membered heteroaryl group containing 1 to 3 ring heteroatoms selected from O, N and S, R 3 H, C1 to C 20 Alkyl, C1 to C 20 Alkylene, C6 to C 22 aryl, or a 5-12 membered heteroaryl group containing 1 to 3 ring heteroatoms selected from O, N and S, n is 0 to (v-1), each R 1 Independently selected from C1 to C 30 Alkyl, C1 to C 30 Alkylene, C1 to C2 substituted by one or more of halogen, -OCF3, -NO2, -CN, -NC, -OH, -OCN, -NCO, alkoxy, epoxy, amino, mercapto, acryloyl, CO2H, CO2 alkyl, aryl and heteroaryl. 30 alkyl, or C1 to C2 substituted by one or more of halogen, -OCF3, -NO2, -CN, -NC, -OH, -OCN, -NCO, alkoxy, epoxy, amino, mercapto, acryloyl, CO2H, CO2 alkyl, aryl and heteroaryl. 30 Alkylene, p is present in an amount up to pmax, and w is 2 to 2000; wherein pmax = 60 / [9*Mw(R 1 )+8], where Mw(R 1 ) is R 1 The molecular weight of the group.
[0114] In an embodiment, R 1 is a C1 to C2 substituted by one to four groups independently selected from halogen, -OCF3, -NO2, -CN, -NC, -OH, -OCN, -NCO, alkoxy, epoxy, amino, mercapto, acryloyl, CO2H, CO2 alkyl, aryl and heteroaryl. 30 In an embodiment, R 1 is a C1 to C2 substituted by one to four groups independently selected from halogen, -OCF3, -NO2, -CN, -NC, -OH, -OCN, -NCO, alkoxy, epoxy, amino, mercapto, acryloyl, CO2H, CO2 alkyl, aryl and heteroaryl. 30 Alkylene.
[0115] In an embodiment, the precursor may include at least polyalkoxysilane (PAOS). In an embodiment, the precursor may also include one or both of tetraethoxysilane (TEOS) and tetrabutoxysilane (TBOS). In an embodiment, the precursor may include polyalkoxysilane (PAOS) synthesized by a non-hydrolysis process. In an embodiment, the precursor may include one or more of the compounds of formula (I) and formula (II) in combination with one or more of tetraethoxysilane (TEOS), tetramethoxysilane (TMOS), tetrabutoxysilane (TBOS), triethoxymethylsilane (TEMS), diethoxy-dimethylsilane (DEDMS), trimethylethoxysilane (TMES) and tetraacetoxysilane (TAcS). In an embodiment, the precursor may also include one or more of the compounds of formula (I) and formula (II) in combination with Si(YR) alone or in combination with one or more of tetraethoxysilane (TEOS), tetramethoxysilane (TMOS), tetrabutoxysilane (TBOS), triethoxymethylsilane (TEMS), diethoxy-dimethylsilane (DEDMS), trimethylethoxysilane (TMES) and tetraacetoxysilane (TAcS). )4-n R n One or more of the compounds of formula (I) and formula (II) in combination with one or more of the silane monomers of the type, wherein YR is a hydrolyzable group and R is a non-hydrolyzable group. Examples of such monomers are given earlier in this paragraph, and these are not intended to limit the scope of monomers that can be used.
[0116] In embodiments, the compound of formula (I) and / or the compound of formula (II) may have a polystyrene equivalent weight average molecular weight (Mw) of about 100 Da to about 300,000 Da. In embodiments, M may be about 100 Da to about 100,000 Da, or about 100 Da to about 90,000 Da, or about 100 Da to about 80,000 Da, or about 100 Da to about 70,000 Da, or about 100 Da to about 60,000 Da, or about 200 Da to about 60,000 Da, or about 300 Da to about 60,000 Da, or about 400 Da to about 60,000 Da. 0 Da, or about 500 Da to about 60,000 Da, or about 600 Da to about 60,000 Da, or about 700 Da to about 60,000 Da, or about 700 Da to about 30,000 Da, or about 800 Da to about 30,000 Da, or about 900 Da to about 30,000 Da, or about 1000 Da to about 30,000 Da, or about 1500 Da to about 30,000 Da.
[0117] In embodiments, compounds of Formula (I) and / or Formula (II) may have a molecular weight polydispersity index of about 1 to about 50. In embodiments, the molecular weight polydispersity index may be about 1 to about 45, or about 1 to about 40, or about 1 to about 30, or about 1 to about 25, or about 1 to about 20, or about 1 to about 15, or about 1 to about 10, or about 1 to about 9, or about 1 to about 8, or about 1 to about 7, or about 1 to about 6, or about 1 to about 5, or about 1 to about 4, or about 1.4 to about 5, or about 1.5 to about 3.5. For example, the molecular weight polydispersity index may be about 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, or 5.0.
[0118] In embodiments, compounds of Formula (I) and / or Formula (II) may have a degree of branching of 0 to about 0.6, about 0.05 to about 0.5, about 0.01 to about 0.1, about 0.03 to about 0.13, about 0.1 to about 0.45, or about 0.2 to about 0.3. Other suitable values include about 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, and 0.6.
[0119] In an embodiment, the first shell member may further include a nanoparticle layer. The nanoparticles of the nanoparticle layer may be one or more of SiO2, TiO2, Al2O3, ZrO2, ZnO2, CaCO3, clay, silver, gold and copper. In an embodiment, the nanoparticle layer may include SiO2 nanoparticles.
[0120] The nanoparticles can have an average diameter of about 1 nm to about 500 nm, about 1 nm to 300 nm, about 1 nm to 200 nm, about 5 nm to about 100 nm, about 10 nm to about 100 nm, and about 30 nm to about 100 nm. For example, in embodiments, the nanoparticles can have an average diameter of about 1 nm, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm.
[0121] In embodiments, the emulsion may be advantageously stabilized by steric hindrance provided by the nanoparticle layer surrounding the droplets and preventing coalescence. In addition, in order to form an emulsion that does not coalesce, the three-phase contact angle between the nanoparticles and the immiscible phase should be close to 90°, since the larger adsorption energy of the nanoparticles at the oil-water interface results in a higher energy input ΔG required for desorption. d , according to the following formula:
[0122] ΔG d =πr 2 γow(1-cosθ) 2
[0123] Among them, ΔG d is the free energy, r is the radius of the nanoparticle, γow is the interfacial tension between the oil phase and the water phase, and θ is the three-phase contact angle. The free energy change of a spherical nanoparticle at the interface depends directly on the water-oil interfacial tension and the radius of the nanoparticle. ΔG d Follow 2 Thus, without being bound by theory, generally larger nanoparticles can more effectively stabilize the emulsion and can affect the pore size between the nanoparticles.
[0124] In embodiments, the pore size can be adjusted by changing the shape of the nanoparticle and / or by using a combination of different nanoparticle sizes. In embodiments, non-spherical irregular nanoparticles can be used, because they can have improved accumulation when forming a nanoparticle layer, and it is believed that this can produce a more dense shell structure. When limited permeability is required, this can be favourable. In other embodiments, the nanoparticle used can have a more regular shape, such as a sphere. Any imagined nanoparticle shape can be used herein.
[0125] In embodiments, the nanoparticles may be substantially free of hydrophobic modifications. In embodiments, the nanoparticles may be substantially free of organic compound modifications. In other embodiments, the nanoparticles may include organic compound modifications. In embodiments, the nanoparticles may be hydrophilic.
[0126] In embodiments, the nanoparticles may include surface modifications such as, but not limited to, linear or branched C1 to C 20 Alkyl groups, surface amino groups, surface methacryloyl groups, surface halogens or surface thiols. These surface modifications allow the nanoparticle surface to have covalently bound organic molecules thereon. When inorganic nanoparticles are disclosed in this document, this means that any of the above surface modifications are included without explicit indication.
[0127] Second shell member
[0128] In an embodiment, the capsule may include a second shell member. The second shell member surrounds the first shell member. The second shell member comprises an inorganic compound. In an embodiment, the second shell member may provide further stability to the capsule and reduce the permeability of the capsule. Without being bound by theory, it is believed that the second shell member may also help improve the performance of the capsule, such as reducing shell permeability and diffusion of the beneficial agent during storage.
[0129] In an embodiment, the second shell member may include one or more of metal oxides, semi-metal oxides, minerals and metals. In an embodiment, the second shell member may include one or more of SiO2, TiO2, Al2O3, ZrO2, ZnO2, CaCO3, Ca2SiO4, Fe2O3, Fe3O4, clay, gold, iron, silver, nickel and copper. In an embodiment, the second shell member may be silicon dioxide. In an embodiment, the second shell member may be silicon dioxide formed from mineralized sodium silicate.
[0130] In embodiments, the second shell member may comprise silica formed from mineralized sodium silicate.In embodiments, the formation of the second shell member comprising silica may form a denser capsule shell due to the deposition of silica within the pores of the first shell member. Fig.10 B shows an embodiment of the housing with a second housing part.
[0131] In an embodiment of the method, the second shell member can be formed by blending a capsule having a first shell member with a solution of a second shell member precursor. The solution of the second shell member precursor can include a water-soluble or oil-soluble second shell member precursor. In an embodiment, the second shell member precursor can be one or more of the compound of formula (I) as defined above, tetraethoxysilane (TEOS), tetramethoxysilane (TMOS), tetrabutoxysilane (TBOS), triethoxymethylsilane (TEMS), diethoxy-dimethylsilane (DEDMS), trimethylethoxysilane (TMES) and tetraacetoxysilane (TAcS). In an embodiment, the second shell member precursor can also include Si(YR )4-n R n One or more of the type silane monomers, wherein YR is a hydrolyzable group and R is a non-hydrolyzable group. Examples of such monomers are given earlier in this paragraph, and these are not intended to limit the scope of monomers that can be used. In an embodiment, the second shell component precursor may include silicates, titanates, aluminates, zirconates and / or zincates. In an embodiment, the second shell component precursor may include carbonates and calcium salts. In an embodiment, the second shell component precursor may include salts of iron, silver, copper, nickel and / or gold. In an embodiment, the second shell component precursor may include zinc, zirconium, silicon, titanium and / or aluminum alkoxides. In an embodiment, the second shell component precursor may include silicate solutions such as sodium silicate, tetrasilicon solution, ferric sulfate and ferric nitrate, titanium alcohol solution, aluminum trialkoxide solution, zinc dialkoxide solution, zirconium alcohol solution, calcium salt solution, carbonate solution. In certain embodiments, the second shell component comprising CaCO3 can be obtained from the combined use of calcium salts and carbonates. In other embodiments, the second shell component comprising CaCO 3 may be obtained from a calcium salt without the addition of carbonates by in situ generation of carbonate ions from CO 2 .
[0132] The second shell component precursor may comprise any suitable combination of any of the above listed compounds.
[0133] In an embodiment, a solution of the second shell component precursor may be added dropwise to the capsule. In an embodiment, the solution of the second shell component precursor and the capsule may be mixed together for about 1 hour to about 24 hours, or about 1 hour to about 12 hours, or about 1 hour to about 5 hours. For example, the solution of the second shell component precursor and the capsule may be mixed together for about 1 hour, 2 hours, 3 hours, 4 hours, or 5 hours. In an embodiment, the solution of the second shell component precursor and the capsule may be mixed together at room temperature or at a high temperature such as 30°C to 60°C, 40°C to 70°C, 40°C to 100°C. For example, the solution of the second shell component precursor and the capsule may be mixed together at room temperature, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 90°C, or 100°C.
[0134] In an embodiment, the solution of the second shell component precursor may include the second shell component precursor in an amount of about 1 wt % to about 50 wt %, or about 1 wt % to about 40 wt %, or about 1 wt % to about 30 wt %, or about 1 wt % to about 20 wt %, or about 5 wt % to about 20 wt %, based on the total weight of the solution of the second shell component precursor. For example, the solution of the second shell component precursor may include the second shell component precursor in an amount of about 1 wt %, 5 wt %, 10 wt %, 20 wt %, 30 wt %, 40 wt %, or 50 wt %, based on the total weight of the solution of the second shell component precursor.
[0135] In embodiments, the capsules may be blended with a solution of the second shell component precursor in the presence of an acid. In embodiments, it may be a weak acid such as HF and acetic acid. In embodiments, the acid may be a strong acid. In embodiments, the strong acid may include one or more of HCl, HNO3, H2SO4, HBr, HI, HClO4, and HClO3. In embodiments, the acid may include HCl. In embodiments, the concentration of the acid in the continuous solution may be from about 0.01M to about 5M, or from about 0.1M to about 5M, or from about 0.1M to about 2M, or from about 0.1M to about 1M. For example, the concentration of the acid in the solution of the second shell component precursor may be about 0.1M, 0.2M, 0.3M, 0.4M, 0.5M, 1M, 1.5M, 2M, 3M, 4M, or 5M.
[0136] In an embodiment, the capsules may be blended with a solution of the second shell component precursor in the presence of a base. In an embodiment, the base may be one or more of a mineral base, a hydroxide such as sodium hydroxide, and ammonia. For example, in an embodiment, the base may be about 10 -5 M to 0.01 M NaOH, or about 10-5 To about 1M ammonia.
[0137] In an embodiment, the method of forming the second shell member may include a change in pH during the method. For example, the process of forming the second shell member may be initiated at an acidic or neutral pH, and then a base may be added during the process to increase the pH. Alternatively, the process of forming the second shell member may be initiated at an alkaline or neutral pH, and then an acid may be added during the process to reduce the pH. In addition, the process of forming the second shell member may be initiated at an acidic or neutral pH, and an acid may be added during the process to further reduce the pH. In addition, the process of forming the second shell member may be initiated at an alkaline or neutral pH, and a base may be added during the process to further increase the pH. Any suitable pH change may be used. In addition, any suitable combination of acid and base may be used in the solution of the second shell member precursor at any time to achieve the desired pH. In an embodiment, the method of forming the second shell member may include maintaining a stable pH with a maximum deviation of + / -0.5 pH units during the process. For example, the process of forming the second shell member may be maintained at an alkaline, acidic or neutral pH. Alternatively, the process of forming the second shell member may be maintained within a specific pH range by controlling the pH using an acid or base. Any suitable pH range may be used. Furthermore, any suitable combination of acid and base may be used in the solution of the second shell component precursor at any time to maintain a stable pH within the desired range.
[0138] nuclear
[0139] In an embodiment, the core (whether oil-based or aqueous) may include one or more beneficial agents, as well as additional components such as excipients, carriers, diluents and other agents. In an embodiment, the core may be a liquid core. In an embodiment, the core may be a gel core. In an embodiment, the core may be aqueous and include a water-based or water-soluble beneficial agent. In an embodiment, the core may be oil-based and may include an oil-based or oil-soluble beneficial agent. In an embodiment, the core has a melting point less than or equal to 15°C. In an embodiment, the core is liquid at the temperature at which it is used to formulate the product. In an embodiment, the core is liquid at and near room temperature.
[0140] Oil-based core
[0141] An oil-based core is defined as an oil phase present in the core of a core-shell capsule, which results from the emulsification of a dispersed oil phase in a continuous aqueous phase; said oil and aqueous phases being substantially immiscible.
[0142] In embodiments, the oil-based core may include a benefit agent of about 1% to 100% by weight based on the gross weight of the core. In embodiments, the core may include a benefit agent of about 25% to 100% by weight based on the gross weight of the core, or a benefit agent of about 50% to 100% by weight based on the gross weight of the core. For example, the core may include a benefit agent of about 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% and 100% by weight based on the gross weight of the core. In embodiments, the core may include a benefit agent of about 80% to 100% by weight based on the gross weight of the core. For example, based on the gross weight of the core, the benefit agent may be 90%, 91%, 92%, 93%, 94%, 96%, 97%, 98% or 99% by weight of the core.
[0143] In embodiments, the oil-soluble and / or oil-based benefit agents may include one or more of the following: chromogens and dyes, fragrance compositions, fragrance raw materials, lubricants, silicone oils, waxes, hydrocarbons, higher fatty acids, essential oils, lipids, skin coolants, vitamins, sunscreens, antioxidants, catalysts, malodor reducers, odor control materials, softeners, insect and moth repellents, colorants, pigments, drugs, medicinal oils, adhesives, bases, drapes and form control agents, lubricants, wrinkle control agents, sanitizers, disinfectants, microbial control agents, Mildew and mildew control agents, antiviral agents, desiccant agents, stain and stain removers, fabric fresheners and freshness extension agents, chlorine bleach odor control agents, dye fixatives, color retention agents, color restoration / restore agents, anti-fading agents, anti-corrosion agents, anti-wear agents, fabric integrity agents, anti-wear agents, anti-pilling agents, defoamers, defoamers, UV protectants, light fade inhibitors, anti-allergenic agents, fabric comfort agents, anti-shrinkage agents, anti-stretch agents, stretch recovery agents, skin care agents and natural actives, dyes, phase change materials, fertilizers, nutrients and herbicides.
[0144] In embodiments, the oil-based core may comprise a fragrance oil.
[0145] In embodiments, the oil-based and / or oil-soluble benefit agent may include a fragrance or fragrance composition.In embodiments, the fragrance composition may include one or more of a fragrance raw material, an essential oil, a malodor reducer, and an odor control agent.
[0146] In various embodiments, the perfume composition may include one or more perfume raw materials. In an embodiment, the perfume composition may include the following by weight, based on the total weight of the perfume composition, in combination or alone: (1) from about 2.5% to about 30%, or from about 5% to about 30%, of perfume raw materials characterized by a logP of less than 3.0 and a boiling point below 250°C; (2) from about 5% to about 30%, or from about 7% to about 25%, of perfume raw materials characterized by a logP of less than or equal to 3.0 and a boiling point greater than or equal to 250°C; (3) from about 35% to about 60%, or from about 40% to about 55%, of perfume raw materials characterized by having a logP greater than 3.0 and a boiling point less than 250°C; and (4) from about 10% to about 45%, or from about 12% to about 40%, of perfume raw materials characterized by having a logP greater than 3.0 and a boiling point greater than 250°C.
[0147] In embodiments, the benefit agent may have an average logP greater than or equal to 1.
[0148] Water-based core
[0149] The water-based core is defined as the aqueous phase present in the core of the core-shell capsule, which results from the emulsification of a dispersed aqueous phase in a continuous oil phase; the oil and aqueous phases being substantially immiscible.
[0150] In embodiments, the water-based core may include about 1% to 99% by weight of a beneficial agent based on the total weight of the core. In embodiments, the core may include about 1% to 75% by weight of a beneficial agent based on the total weight of the core, or about 1% to 50% by weight of a beneficial agent based on the total weight of the core. For example, the core may include about 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% and 50% by weight of a beneficial agent based on the total weight of the core. In embodiments, the core may include about 1% to 20%, 30% to 50% by weight, or 20% to 40% by weight of a beneficial agent based on the total weight of the core.
[0151] In an embodiment, the water-based and / or water-soluble benefit agent is one or more of the following: a fragrance composition, a fragrance raw material, a fragrance, a skin coolant, a vitamin, a sunscreen, an antioxidant, a glycerin, a bleach encapsulate, a chelating agent, an antistatic agent, an insect and moth repellent, a colorant, an antioxidant, a sanitizer, a disinfectant, a microbial control agent, a mold control agent, a mildew control agent, an antiviral agent, a desiccant, a stain repellent, a detergent, a chlorine bleach odor control agent, a dye fixative, a dye transfer inhibitor, a color maintenance agent, an optical brightener, Color restoration / rejuvenation agents, anti-fading agents, whiteness enhancers, anti-corrosion agents, anti-wear agents, fabric integrity agents, anti-wear agents, anti-pilling agents, defoamers, defoaming agents, UV protectants, photofade inhibitors, anti-allergenic agents, enzymes, water repellents, fabric comfort agents, anti-shrinkage agents, anti-stretch agents, stretch recovery agents, skin care agents and natural actives, antimicrobial actives, antiperspirant actives, cationic polymers, dyes, metal catalysts, non-metal catalysts, activators, preformed peroxycarboxylic acids, diacyl peroxides, hydrogen peroxide sources, and enzymes.
[0152] In an embodiment, the water-based and / or water-soluble benefit agent may include one or more metal catalysts. In an embodiment, the metal catalyst may include one or more of the following: dichloro-1,4-diethyl-1,4,8,11-tetraazabicyclo[6.6.2]hexadecanemanganese(II); and dichloro-1,4-dimethyl-1,4,8,11-tetraazabicyclo[6.6.2]hexadecanemanganese(II). In an embodiment, the non-metal catalyst may include one or more of the following: 2-[3-[(2-hexyldodecyl)oxy]-2-(sulfoxy)propyl]-3,4-dihydroisoquinolinium, inner salt; 3,4-dihydro-2-[3-[(2-pentylundecyl)oxy]-2-(sulfoxy)propyl]isoquinolinium, inner salt; 2-[3-[(2-butyldecyl)oxy]-2-(sulfoxy)propyl]-3,4-dihydroisoquinolinium, inner salt. Hydroisoquinolinium, inner salt; 3,4-dihydro-2-[3-(octadecyloxy)-2-(sulfooxy)propyl]isoquinolinium, inner salt; 2-[3-(hexadecyloxy)-2-(sulfooxy)propyl]-3,4-dihydroisoquinolinium, inner salt; 3,4-dihydro-2-[2-(sulfooxy)-3-(tetradecyloxy)propyl]isoquinolinium, inner salt; 2-[3-(dodecyloxy)-2-(sulfooxy)propyl]-3,4 -dihydroisoquinolinium, inner salt; 2-[3-[(3-hexyldecyl)oxy]-2-(sulfooxy)propyl]-3,4-dihydroisoquinolinium, inner salt; 3,4-dihydro-2-[3-[(2-pentylnonyl)oxy]-2-(sulfooxy)propyl]isoquinolinium, inner salt; 3,4-dihydro-2-[3-[(2-propylheptyl)oxy]-2-(sulfooxy)propyl]isoquinolinium, inner salt; 2-[3-[(2-butyl 2-[3-(decyloxy)-2-(sulfooxy)propyl]-3,4-dihydroisoquinolinium, inner salt; 3,4-dihydro-2-[3-(octyloxy)-2-(sulfooxy)propyl]isoquinolinium, inner salt; and 2-[3-[(2-ethylhexyl)oxy]-2-(sulfooxy)propyl]-3,4-dihydroisoquinolinium, inner salt.
[0153] In an embodiment, the water-based and / or water-soluble benefit agent may include one or more activators. In an embodiment, the activator may include one or more of the following: tetraacetylethylenediamine (TAED); benzoyl caprolactam (BzCL); 4-nitrobenzoyl caprolactam; 3-chlorobenzoyl caprolactam; benzoyloxybenzene sulfonate (BOBS); nonanoyloxybenzene sulfonate (NOBS); phenyl benzoate (PhBz); decanoyloxybenzene sulfonate (C 10-OBS); benzoyl valerolactam (BZVL); octanoyloxybenzenesulfonate (C8-OBS); perhydrolyzable esters; 4-[N-(nonanoyl)aminocaproyloxy]-benzenesulfonic acid sodium salt (NACA-OBS); dodecanoyloxybenzenesulfonate (LOBS or C 12 -OBS); 10-undecenoyloxybenzenesulfonate (UDOBS or C with unsaturation at position 10); 11 -OBS); decanoyloxybenzoic acid (DOBA); (6-octanoylaminohexanoyl)oxybenzenesulfonate; (6-nonanoylaminohexanoyl)oxybenzenesulfonate; and (6-decanoylaminohexanoyl)oxybenzenesulfonate.
[0154] In an embodiment, the water-based and / or water-soluble benefit agent may include one or more preformed peroxycarboxylic acids. In an embodiment, the peroxycarboxylic acid may include one or more of the following: peroxymonosulfuric acid; perimidic acid; percarbonic acid; percarboxylic acids and salts of said acids; phthalimidoperoxycaproic acid; aminoperoxyacids; 1,12-diperoxydodecanedioic acid; and monoperoxyphthalic acid (hexahydrated magnesium salt), wherein the aminoperoxyacid may include N,N'-terephthaloyl-bis(6-aminocaproic acid), monononanamide of peroxysuccinic acid (NAPSA) or peroxyadipic acid (NAPAA), or N-nonanoylaminoperoxycaproic acid (NAPCA).
[0155] In an embodiment, the water-based and / or water-soluble benefit agent may include one or more diacyl peroxides. In an embodiment, the diacyl peroxide may include one or more of dinonanoyl peroxide, didecanoyl peroxide, didecanoyl peroxide, diundecanoyl peroxide, dilauroyl peroxide and dibenzoyl peroxide, di-(3,5,5-trimethylhexanoyl) peroxide, wherein the diacyl peroxide may be clathrate.
[0156] In an embodiment, the water-based and / or water-soluble benefit agent may include one or more hydrogen peroxides. In an embodiment, the hydrogen peroxide source may include one or more of perborates, percarbonates, peroxyhydrates, peroxides, persulfates, and mixtures thereof, in one aspect, the hydrogen peroxide source may include sodium perborate, in one aspect, the sodium perborate may include monohydrate or tetrahydrate, sodium pyrophosphate peroxyhydrate, urea peroxyhydrate, trisodium phosphate peroxyhydrate, and sodium peroxide.
[0157] In embodiments, the water-based and / or water-soluble benefit agent may include one or more enzymes. In embodiments, the enzyme may include one or more of the following: peroxidase, protease, lipase, phospholipase, cellulase, cellobiohydrolase, cellobiose dehydrogenase, esterase, cutinase, pectinase, mannanase, pectate lyase, keratinase, reductase, oxidase, phenoloxidase, lipoxygenase, ligninase, pullulanase, tannase, pentosanase, glucanase, arabinosidase, hyaluronidase, chondroitinase, laccase, amylase and DNase.
[0158] In embodiments, the water-based and / or water-soluble benefit agent may include a fragrance or fragrance composition.In embodiments, the fragrance composition may include one or more of a fragrance raw material, an essential oil, a malodor reducer, and an odor control agent.
[0159] In various embodiments, the perfume composition may include one or more perfume raw materials. In an embodiment, the perfume composition may include the following by weight, based on the total weight of the perfume composition, in combination or alone: (1) about 35% to about 60%, or about 40% to about 55% of a first perfume raw material characterized by a logP of less than 1.5 and a boiling point below 250°C; (2) about 10% to about 45%, or about 12% to about 40% of a second perfume raw material characterized by a logP of less than or equal to 1.5 and a boiling point greater than or equal to 250°C; (3) about 2.5% to about 30%, or about 5% to about 30% of a third perfume raw material characterized by having a logP greater than 1.5 and a boiling point less than 250°C; and (4) about 5% to about 30%, or about 7% to about 25% of a fourth perfume raw material characterized by having a logP greater than 1.5 and a boiling point greater than 250°C.
[0160] In embodiments, the benefit agent may have an average logP less than or equal to 1.
[0161] Method for preparing oil-based core capsules
[0162] In embodiments of the method of making capsules having an oil-based core, the oil phase may comprise oil-based and / or oil-soluble benefit agents and precursors.
[0163] In embodiments, the precursor is present in an amount of about 1 wt % to about 50 wt % based on the total weight of the oil phase. Other suitable amounts include about 1 wt % to about 15 wt %, about 5 wt % to about 30 wt %, about 10 wt % to about 20 wt %, about 15 wt % to about 40 wt %, about 25 wt % to about 45 wt %, or about 15 wt % to about 50 wt %, based on the total weight of the oil phase. For example, the oil phase may include about 1 wt %, 2 wt %, 3 wt %, 4 wt %, 5 wt %, 6 wt %, 7 wt %, 8 wt %, 9 wt %, 10 wt %, 11 wt %, 12 wt %, 13 wt %, 14 wt %, 15 wt %, 16 wt %, 17 wt %, 18 wt %, 19 wt %, 20 wt %, 22 wt %, 24 wt %, 26 wt %, 28 wt %, 30 wt %, 32 wt %, 34 wt %, 36 wt %, 38 wt %, 40 wt %, 42 wt %, 44 wt %, 46 wt %, 48 wt %, or 50 wt %, based on the total weight of the oil phase.
[0164] In an embodiment, the oil phase may contain about 10% to about 99% by weight, or about 20% to about 99% by weight, about 40% to about 99% by weight, or about 50% to about 99% by weight, or about 50% to about 90% by weight of a beneficial agent based on the total weight of the oil phase before emulsification. For example, the beneficial agent may be present in an amount of about 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80% or 90% by weight based on the total weight of the oil phase.
[0165] The oil phase may also include one or more oil-soluble core modifiers. For example, the oil-soluble core modifier may be one or more of a distribution modifier and / or a density modifier. In an embodiment, the distribution modifier may include an oil-soluble material having a logP greater than about 1, or greater than about 2, or greater than about 3, or greater than about 4, or greater than about 5, or greater than about 6, or greater than about 7, or greater than about 8, or greater than about 9, or greater than about 10, or greater than about 11. In an embodiment, the distribution modifier may include an oil-soluble material having a density greater than or equal to 1 gram / cubic centimeter. In an embodiment, the distribution modifier may include one or more of the following: C4-C 24Monoesters, diesters and triesters of fatty acids and glycerol; fatty acid esters of polyglycerol oligomers; polyalphaolefins; silicone oils; crosslinked silicones containing polyether-substituted structural units and acrylate crosslinks; polyglycerol ether siloxane crosspolymers; alkyl-substituted celluloses; hydroxypropyl cellulose; fatty acid esters of acrylic acid or methacrylic acid with side chain crystalline groups; copolymers of ethylene, including ethylene and vinyl acetate, ethylene and vinyl alcohol, ethylene / acrylic acid elastomers; acetyl caryophyllene, hexose, butyl oleate, hydrogenated castor oil, sucrose benzoate, lauric acid, palmitic acid, stearic acid, tetradecanol, hexadecanol, 1-octanediol, isopropyl myristate, castor oil, mineral oil, isoparaffin, caprylic triglyceride , soybean oil, vegetable oil, brominated vegetable oil, heptane bromide, sucrose octaacetate, geranyl palmitate, acetylated caryophyllene, sucrose benzoate, butyl oleate, silicone, polydimethylsiloxane, vitamin E, decamethylcyclopentasiloxane, dodecamethylcyclohexasiloxane, sucrose soybean ester, sucrose stearate, sucrose soyanate, lauryl alcohol, 1-tetradecanol, 1-hexadecanol, cetyl alcohol, 1-octadecanol, 1-docosecanol, 2-octyl-1-dodecanol, fragrance oil, in one aspect, a fragrance oil having logP>5, in one aspect, the fragrance oil can be selected from the group consisting of: octadecanoic acid, octadecyl esters; 2,6,10,15,19,23-hexamethyl-tetracosane ; Octadecanoic acid diester soluble in 1,2,3-propanetriol; 1,1'-[(3,7-dimethyl-6-octenylidene)bis(oxy)]bis-isotridecane; octadecyl tetradecanoate; (all-E)-2,6,10,15,19,23-hexamethyl-2,6,10,14,18,22-tetracosahexaene; tricosane; docosane; dodecyl hexadecanoate; didodecyl 1,2-benzenedicarboxylate; 1,2,3-propanetriol decanoate; 11,11-bis[(3,7-dimethyl-6-octenyl)oxy]-1-undecene; heneicosane; [2-[bis[(3,7-dimethyl-2,6-octadienyl)oxy]methyl]-1-benzene; 11,11-Bis[(3,7-dimethyl-2,6-octadienyl)oxy]-1-undecene; [2-[Bis[(1-vinyl-1,5-dimethyl-4-hexenyl)oxy]methyl]-1-benzene; tetradecyl dodecanoate; [2R-[2R*(4R*,8R*)]]-3,4-dihydro-2,5,7,8-tetramethyl-2-(4,8,12-trimethyltridecyl)-2H-1-benzopyran-6-ol; octadecyl octanoate; eicosane; [2R*(4R*,8R*)]-3,4-dihydro-2,5,8-trimethyl-2-(4,8,12-trimethyltridecyl)-2H-1-benzopyran-6-ol;[1R-[1α[E(S*)],2β,4aβ,8aα]]-1-[6-(2,2-dimethyl-6-methylenecyclohexyl)-4-methyl-3-hexenyl]decahydro-2,5,5,8a-tetramethyl-2-naphthol; [2R-[2R*(4R*,8R*)]]-3,4-dihydro-2,7,8-trimethyl-2-(4,8,12-trimethyltridecyl)-2H-1-benzopyran-6-ol; heptanoic acid octadecyl ester; nonadecane; (2E,4E,6E,8E,10E,12E,14E,16E)-2,6,11,15-tetramethyl-17-(2,6,6-trimethyl-1-cyclohexen-1-yl)-2,4,6,8,10 ,12,14,16-heptadecadecene aldehyde; [2R-[2R*(4R*,8R*)]]-3,4-dihydro-2,8-dimethyl-2-(4,8,12-trimethyltridecyl)-2H-1-benzopyran-6-ol; 2-ethylhexyl hexadecanoate; didecyl 1,2-benzenedicarboxylate; octadecane; 2-[[2-(phenylmethylene)octylene]amino]-1-vinyl-1,5-dimethyl-4-hexenyl benzoate; 3-methylbutyl octadecanoate; decanoate with 1,2,3-propanetriol octanoate; heptadecane; 7,11,15-trimethyl-3-methylene-1-hexadecene; decyl dodecanoate; butyl octadecanoate; bis(2-ethylhexyl) sebacate; [2,2- Bis[(3,7-dimethyl-6-octenyl)oxy]ethyl]-benzene; [2,2-bis[(3,7-dimethyl-2,6-octadienyl)oxy]ethyl]-benzene; (Z)-9-octadecanoic acid butyl ester; 1,2,3-propanetriol octanoate; hexadecane; 4-(5-methyl-1-methylene-4-hexenyl)-1-(4-methyl-3-pentenyl)-cyclohexene; [R-[R*,R*-(E)]]-3,7,11,15-tetramethyl-2-hexadecene-1-ol acetate; hexadecanoic acid butyl ester; octadecanoic acid ethyl ester; 2-octyl-1-dodecanol; pentadecane; tetradecanoic acid hexyl ester; decyl decanoate; octadecyl acetate; hexadecanoic acid 2-methylpropyl ester; (Z)-9-octadecanoic acid ethyl ester; Ethyl heptadecanoate; Methyl octadecanoate; Tetradecane; 3-methylbutyl tetradecanoate; [R-[R*,R*-(E)]]-3,7,11,15-tetramethyl-2-hexadecene-1-ol; 3,7,11,15-tetramethyl-2-hexadecene-1-ol; 1-methylethyl hexadecanoate; 1,1'-(3,7-dimethyl-6-octenylidene)bis-1H-indole; Octadecanoic acid; Decamethyl-cyclopentasiloxane; 2-[[2-(phenylmethylene)octylene]amino]-3-methylbutyl benzoate; Ethyl (Z,Z)-9,12-octadecadienoate; 1-octadecyl alcohol; Dioctyl adipate; Methyl (Z)-9-octadecanoate; 2-hydroxypropyl octadecanoate; Butyl tetradecanoate; Hexyl dodecanoate;(Z,Z,Z)-9,12,15-octadecatetrienoic acid ethyl ester; hexadecanoic acid ethyl ester; 1-hexadecanoic acid acetate; (Z)-9-octadecanoic acid; adipate bis (2-ethylhexyl) ester; 1,8,11,14-heptadecatetraene; 1,8,11,14-heptadecatetraene; 1,8,11,14-heptadecatetraene; (Z)-9-octadecene-1-ol; tetradecanoic acid-2-methylpropyl ester; nonanoic acid-1-methyl-1,2-ethylenediester; tridecane; [1S-(1α,4α,4aα,6α,8aβ)]-dehydro-1,6-dimethyl-4-(1-methylethyl)-naphthalene didehydro derivative; 3,7,11,15-tetramethyl-1-hexadecyn-3-ol; (Z,Z) -9,12-octadecadienoic acid methyl ester; 1-heptadecanol; 3,7,11,15-tetramethyl-6,10,14-hexadecatrieno-3-ol; benzoic acid-2-[[[4-(4-methyl-3-pentenyl)-3-cyclohexen-1-yl]methylene]amino]-methyl ester; (Z,Z)-9,12-octadecadienoic acid; 1,1'-oxybis-2-nonene; santalinol phenylacetate; 10-undecanoic acid heptyl ester; (Z,Z,Z)-9,12,15-octadecadienoic acid methyl ester; octadecanoic acid monoester with 1,2,3-propanetriol; pentyl dodecanoate; nonyl octanoate; ethyl pentadecanate; methyl hexadecanoate; 4-methylphenyl dodecanoate; 3-methylbutyl dodecanoate; 1-methyl tetradecanoate ethyl ester; hexadecanoic acid; [1R-(1α,4aβ,4bα,7β,8aβ,10aα)]-1-phenanthrenecarboxylic acid tetradecahydro-1,4a-dimethyl-7-(1-methylethyl)-methyl ester; 1-hexadecanol; dodecane; 6,10,14-trimethyl-2-pentadecane; 9-heptadecanone; [1R-(1α,4aβ,4bα,10aα)]-1-phenanthrenecarboxylic acid tetradecahydro-1,4a-dimethyl-7-(1-methylethyl)-acetate; isohexadecanol; 2-methylpropyl dodecanoate; hexadecene nitrile; 2,3-dihydroxypropyl octadecanoate; isododecane; tetradecahydro-1,4a-dimethyl-7-(1-methyl 1-Phenanthrenecarboxylic acid 1,2,3,4,4a,4b,5,6,7,8,10,10a-dodecahydro-1,4a-dimethyl-7-(1-methylethyl)-methyl ester; (Z)-9-octadecenoic acid ester with 1,2,3-propanetriol; 9,12,15-octadecatrienoic acid; (E,E,E)-2,6,6,9-tetramethyl-1,4,8-cycloundecadiene;Dodecahydro-1,4a-dimethyl-7-(1-methylethyl)-1-phenanthrenol; 3,4,5-trihydroxy-dodecyl benzoate; η-1H-indol-1-yl-α,α,ε-1H-indole-1-heptanol; cyclododecane; (Z)-9-hexadecenoic acid; 2-[[2-(phenylmethylene)heptyl]amino]-methyl benzoate; (Z)-9-octadecenoic acid 2,3-dihydroxypropyl ester; trans-5,6,7,8-tetrahydro-3,5,5,6,7,8,8-heptamethyl-2-naphthaldehyde; 1-vinyl-1,5-dimethyl-4-hexenyl octanoate; and 2-hexadecanone. ;
[0166] In embodiments, the density modifier may include one or more of the following: brominated vegetable oil; sucrose octaacetate; heptane bromide; titanium dioxide; zinc oxide; iron oxide; cobalt oxide; nickel oxide; silver oxide; copper oxide; zirconium oxide; silicon dioxide; silver; zinc; iron; cobalt; nickel; copper; epoxidized soybean oil polyol; 2,3-dihydro-1,1,3,3,5-pentamethyl-4,6-dinitro-1h-indene; (2-bromovinyl)-benzene; 2-methoxy-4-(1-propenyl)phenyl phenylacetate; 1-(2,5-dimethyl-3-thienyl)-ethanone; 3-(4-methoxyphenyl)-ethyl oxiranecarboxylate; 2-[(1-hydroxy-3-phenylbutyl)amino]-methyl benzoate; 1,3-benzodioxacyclopentane Ethyl pentene-5-carboxylate; 5-(2-propenyl)-1,3-benzodioxole; 4-methoxy-benzoic acid; α-(trichloromethyl)-acetic acid benzyl alcohol ester; 2-methoxy-4-(2-propenyl)-phenol ester; 2-methoxy-4-(2-propenyl)-benzoic acid phenol ester; 3-phenyl-benzoic acid 2-propen-1-ol ester; 3-methylphenyl phenylacetate; 1-(1,1-dimethylethyl)-3,4,5-trimethyl-2,6-dinitro-benzene; 4-methylphenyl phenylacetate; phenyl methyl phenylacetate; (4-methoxyphenyl) methyl phenylacetate; 2-propenoic acid 3-phenyl-phenylmethyl ester; 2-propenoic acid 3-phenyl-2-phenylmethyl ester; 2-methoxy-4-phenylacetate (2-propenyl)phenyl ester; 2-(methylthio)-phenol; benzoic acid 2-[[3-(1,3-benzodioxol-5-yl)-2-methylpropylidene]amino]-methyl ester; benzoic acid 2-[[3-(4-methoxyphenyl)-2-methylpropylidene]amino]-methyl ester; 3,5-dimethoxy-benzoic acid; benzoic acid 2-hydroxy-phenyl ester; benzoic acid 2-hydroxy-phenyl methyl ester; benzoic acid 2-hydroxy-ethyl ester; benzoic acid 2-hydroxy-methyl ester; benzoic acid 2-amino-methyl ester; 2-hydroxy-1,2-diphenyl-ethanone; benzoic acid 4-hydroxy-ethyl ester; benzoic acid phenyl methyl ester; 5-(1-propenyl)-1,3-benzodioxole; 2-methyl-benzothiazole; 10,11-dihydro- 5h-dibenzo[a,d]cyclohepten-5-one; 3-phenyl-ethyl oxiranecarboxylate; 4-methoxy-methyl benzoate; 2-propenoic acid 3-phenyl-3-phenyl-2-propene ester; 4-methyl-8-methylene-tricyclo[3.3.1.13,7]decan-2-ol; 4-methyl-8-methylene-acetic acid tricyclo[3.3.1.13,7]decan-2-ol ester; bis(2,4-dihydroxyphenyl)-methanone; (2-hydroxy-4-methoxyphenyl)phenyl-methanone; dibenzofuran; 2-amino-2-phenylethyl benzoate; 1-(naphthyl)-ethanone; 2,2'-[thiobis(methylene)]bis-furan; 1,2,3-propanetriol tripropionate; (e)-3-phenyl-2-propenoic acid;4-Ethyl-2,6-dimethoxyphenol; methylphenyl disulfide; benzoic acid 2-[[(4-methoxyphenyl)methylene]amino]-methyl ester; (z)-3-(2-methoxyphenyl)-2-propenoic acid; 8-quinolinol; bis(phenylmethyl) disulfide; 1,2-propylene glycol dibenzoate; 1-bromo-4-vinyl-benzene; di-2-propenyl trisulfide; (e)-2,6-dimethoxy-4-(1-propenyl)-phenol; (2-isothiocyanatoethyl)-benzene; benzoic acid 2-hydroxy-5-methyl-methyl ester; 3,5-dimethyl-1,2,4-trithiolane; propionic acid 2-(methyldisulfide)-ethyl ester; benzoic acid 2-hydroxy-cyclohexyl ester; benzoic acid 2-[(1-oxypropyl) )amino]-methyl ester; s-(4,5-dihydro-2-methyl-3-furanyl)ethylsulfate; 2-(acetylamino)-methyl benzoate; 2,4,6-trimethyl-1,3,5-trithiane; 2-amino-propyl benzoate; 1-naphthyl butyrate; 2,4-dihydroxy-3-methyl-methyl benzoate; methyl 2-propenyl trisulfide; 2-furanmethanol benzoate; 2-hydroxy-5-methyl-ethyl benzoate; (2,2-dichloro-1-methylcyclopropyl)-benzene; 5-ethyl-2-thiophenecarboxaldehyde; benzoic acid [(phenylmethylene)amino]-methyl ester; hexahydro-2',3a-dimethyl-spiro[1,3-dithio[4,5-b]furan-2,3'(2'h)-furan]; 5-(di 1,3-benzodioxole; 1,3,3a,4,5,6,7,8,9,10,11,13a-dodecahydro-cyclododeca[c]furan; 2-methoxyphenyl phenylacetate; 2-benzofurancarboxaldehyde; 3-methyl-1,2,4-trithiane; 2,2'-[dithiobis(methylene)]bis-furan; (e,e)-1,7-bis(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione; 2,4-dihydroxy-3,6-dimethyl-methyl benzoate; 2-hydroxy-4-methoxy-methyl benzoate; 2-methyl-1,3-benzodioxol-5-ylmethyl propionate; 3,5-diethyl-1,2,4-trithiacyclopentane; 3, 5-Bis(1-methylethyl)-1,2,4-trithiolane; 2-[(methyldisulfide)methyl]-furan; dimethyl tetrasulfide; α-(2-furylmethylene)-phenylacetaldehyde; 3-methoxy-benzoic acid; s-phenylcarboxythioic acid methyl ester; 2-methoxy-methyl benzoate; 2-hydroxy-4-methylphenyl benzoate; 2-hydroxy-propyl benzoate; 3-(2-methoxyphenyl)-2-propenoic acid; 3-(3-methoxyphenyl)-2-propenoic acid; 2-hydroxy-4-methoxy-6-methyl-ethyl benzoate; 2-hydroxy-5-methyl-benzaldehyde; 1,2,3-propanetriol tribenzoate; 4-methylphenyl benzoate; 2-furancarboxylic acid propyl ester; 2-hydroxy-2-methylphenyl benzoate;4-Hydroxy-3-methoxy-ethyl benzoate; 3-phenyl-2-propenoic acid; 1,3-dibromo-2-methoxy-4-methyl-5-nitro-benzene; (isothiocyanatomethyl)-benzene; 2-propenoic acid 3-(2-furyl)-ethyl ester; 4-methoxy-benzylmercaptan; 2-thienylmercaptan; 1,1'-[(2-phenylethylidene)bis(oxymethylene)]bis-benzene; 2,6-dimethoxy-4-(2-propenyl)-phenol; 2-[(2-phenylethylidene)amino]-methyl benzoate; β-oxo-4-methylphenyl phenylpropanoate; η-1h-indol-3-yl-α,α,ε-trimethyl-1h-indol-3-heptanol; 2-hydroxy-3-methyl-2-butenyl benzoate; 1,3- Benzodioxole-5-propanol-α-methyl-acetate; 2,2'-dithiobis-thiophene; 2-hydroxy-benzoic acid; 2-hydroxy-4-methyl-benzaldehyde; methylbenzyl disulfide; 2-phenylethyl 2-furancarboxylate; 2-methoxy-benzenethiol; benzoic acid 2-[[(4-hydroxy-3-methoxyphenyl)methylene]amino]-methyl ester; 2-(4-methylphenoxy)-1-(2-phenylethoxy)-ethanol; phenylacetic acid 3-phenyl-2-propenyl ester; benzoic acid 2-amino-2-propenyl ester; 1,5-dimethyl-bicyclo[3.2.1]octan-8-one oxime; 2-thiophenethiol; 2-methoxy-4-(1-propenyl)-carboxylic acid phenol ester; benzoic acid 2-amino-cyclohexyl ester; 4-vinyl-2-methoxy-phenol; 2-hydroxy-2-(1-methylethoxy)ethyl benzoate; 1-[4-(1,1-dimethylethyl)-2,6-dimethyl-3,5-dinitrophenyl]-ethanone; 1-(1,1-dimethylethyl)-3,5-dimethyl-2,4,6-trinitro-benzene; 3-(4-methoxyphenyl)-2-propenoic acid; 1-(1,1-dimethylethyl)-2-methoxy-4-methyl-3,5-dinitro-benzene; 1,2-phthalic acid diethyl ester; 1-(3,4-dihydro-2h-pyrrol-5-yl)-ethanone; 2-(methylamino)-methyl benzoate; 7-ethoxy-4-methyl-2h-1-benzopyran-2-one; 2-hydroxy-benzoic acid 2-phenylethyl ester; 2-amino-ethyl benzoate; 3-phenyl-2-aminobenzoic acid 2-propene-1-ol ester; 4-chloro-3,5-dimethyl-phenol; diphenyl disulfide; 1-naphthol; [1,1'-biphenyl]-2-ol; α-phenyl-benzyl alcohol; 2-naphthalenethiol; 1-(2-naphthyl)-ethanone; 2-methoxy-4-(1-propene)-acetic acid phenol ester; 2-naphthol benzoate; phenyl benzoate; 2-[3-(2-chlorophenyl)propyl]-pyridine; 4-hydroxy-propyl benzoate; 1-(1-naphthyl)-ethanone; 3-[(2-furanylmethyl)thio]-ethyl propionate; 1,3-diphenyl-2-propene-1-one; 3-pyridinecarboxylic acid phenyl methyl ester; 2-phenylethyl benzoate;(e,e)-1-[5-(1,3-benzodioxol-5-yl)-1-oxo-2,4-pentadienyl]-piperidine; and benzothiazole. ;
[0167] In embodiments of methods of making capsules with an oil-based core, the aqueous phase (continuous phase) may comprise water, an acid, and nanoparticles. In embodiments, the aqueous phase, at least when blended with the oil phase, has a pH of about 1 to about 14. Other suitable pHs include about 1 to about 5, about 2 to about 7, about 6 to about 7, about 1 to about 4, about 3 to about 7, about 7 to 14, about 8 to 10, about 9 to 11, or about 7 to 9. For example, the pH of the aqueous phase may be about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, or 14.
[0168] In embodiments, the acid may be a strong acid. In embodiments, the strong acid may include one or more of HCl, HNO3, H2SO4, HBr, HI, HClO4, and HClO3. In embodiments, the acid may include HCl. In embodiments, the concentration of the acid in the continuous solution may be about 0.01M to about 5M, or about 0.1M to about 5M, or about 0.1M to about 2M, or about 0.1M to about 1M. For example, the concentration of the acid in the continuous solution may be about 0.1M, 0.2M, 0.3M, 0.4M, 0.5M, 1M, 1.5M, 2M, 3M, 4M, or 5M.
[0169] In embodiments, the acid may be a weak acid such as HF and acetic acid.
[0170] In embodiments of the method of preparing capsules having an oil-based core, the aqueous phase (continuous phase) may contain a base. In embodiments, the base may be one or more of a mineral base, a hydroxide such as sodium hydroxide, and ammonia. For example, in embodiments, the base may be about 10 -5 M to 0.01 M NaOH, or about 10 -5 To about 1M ammonia.
[0171] In embodiments of the method for preparing capsules with an oil-based core, pH can be changed throughout the process by adding acid and / or alkali. For example, the method can be initiated with an aqueous phase at an acidic or neutral pH, and then an alkali can be added during the process to increase the pH value. Alternatively, the method can be initiated with an aqueous phase at an alkaline or neutral pH, and then an acid can be added during the process to reduce the pH value. In addition, the method can be initiated with an aqueous phase at an acidic or neutral pH, and then an acid can be added during the process to further reduce the pH value. In addition, the method can be initiated with an aqueous phase at an alkaline or neutral pH, and then an alkali can be added during the process to further increase the pH value. Any suitable pH change can be used. In addition, any suitable combination of acid and alkali can be used in the method at any time to reach the desired pH.
[0172] Any of the above nanoparticles can be used in the aqueous phase. In embodiments, the nanoparticles can be present in an amount of about 0.01 wt % to about 10 wt % based on the gross weight of the aqueous phase. Other suitable amounts include about 0.05 wt % to about 5 wt %, about 1 wt % to about 10 wt %, about 5 wt % to about 8 wt %, about 2 wt % to about 7 wt %, or about 0.1 wt % to about 1 wt %. For example, the nanoparticles can be present in an amount of about 0.01 wt%, 0.02 wt%, 0.03 wt%, 0.04 wt%, 0.05 wt%, 0.06 wt%, 0.07 wt%, 0.08 wt%, 0.09 wt%, 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, or 10 wt% based on the total weight of the aqueous phase.
[0173] In embodiments, the method may include blending the oil phase and the water phase in a ratio of about 1:10 to about 1:1, about 1:9 to about 1:1, about 1:5 to about 1:1, about 1:3 to about 1:1, about 1:5 to about 1:2, about 1:3 to about 1:1.5. Other suitable ratios include about 1:10, 1:9, 1:8, 1:7, 1:6, 1:5, 1:4, 1:3, 1:2, 2:5, 3:5, 1:1.5, or 1:1.
[0174] Method for preparing water-containing core capsules
[0175] In embodiments of the method of making a capsule having an aqueous core, the aqueous phase may comprise an aqueous benefit agent.
[0176] In an embodiment, the aqueous phase may contain from about 1% to about 99% by weight, or from about 20% to about 99% by weight, from about 40% to about 99% by weight, or from about 50% to about 99% by weight, or from about 50% to about 90% by weight of a beneficial agent based on the total weight of the aqueous phase prior to emulsification. For example, the beneficial agent may be present in an amount of about 1%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80% or 90% by weight based on the total weight of the aqueous phase.
[0177] In embodiments, the aqueous phase may also include one or more core regulators. For example, the aqueous core regulator may be one or more of a pH regulator, a viscosity regulator, an ionic strength regulator, an aesthetic regulator, a density regulator, and a gelling agent. In embodiments, a pH regulator may be incorporated to produce a desired pH in the core. In embodiments, the pH regulator may include any base or acid known to those skilled in the art of detergent manufacturing, for example, the following bases: carbonates and hydroxycarbonates of alkali metals or alkaline earth metals, such as sodium hydroxide or potassium hydroxide carbonates; oxides and hydroxides of alkali metals or alkaline earth metals, such as magnesium oxide, sodium hydroxide, or potassium hydroxide; citrates, fumarates, succinates, tartrates, maleates, ascorbates, alkali metal or alkaline earth metal silicates, such as sodium citrate; the following acids: citric acid, fumaric acid, succinic acid, tartaric acid, malic acid, ascorbic acid, phosphoric acid, hydrochloric acid, sulfuric acid, sulfurous acid.
[0178] In an embodiment, the viscosity modifier may include nanofibrillated and microfibrillated cellulose of bacterial or plant origin, uncoated or coated with a polymer thickener; non-polymeric crystalline hydroxy-functional materials, such as crystallizable glycerides, including hydrogenated castor oil; polymer structurants of natural origin such as hydroxyethyl cellulose, hydrophobically modified hydroxyethyl cellulose, carboxymethyl cellulose, polysaccharide derivatives. Suitable polysaccharide derivatives include: pectin, alginate, arabinogalactan (gum arabic), carrageenan, gellan gum, xanthan gum, guar gum. Suitable viscosity modifiers that may be incorporated include synthetic polymeric structurants, such as polycarboxylates, polyacrylates, hydrophobically modified ethoxylated polyurethanes, hydrophobically modified nonionic polyols; wherein the polycarboxylate polymer may include one or more of polyacrylates and polymethacrylates; unsaturated monocarbonic or dicarbonic acids and (meth) acrylic acid C1-C1 30 Copolymers of alkyl esters.
[0179] In embodiments, the ionic strength modifier may include one or more carboxylic acids, polycarboxylates, phosphates, phosphonates, polyphosphates, polyphosphonates, and borates. In embodiments, the ionic strength modifier may also include one or more ionic species, such as homopolymers and copolymers of oxydisuccinic acid, aconitic acid, citric acid, tartaric acid, malic acid, maleic acid, fumaric acid, succinic acid, sebacic acid, citraconic acid, adipic acid, itaconic acid, dodecanoic acid, acrylic acid, maleic acid, calcium, magnesium, iron, manganese, cobalt, copper, and zinc ions.
[0180] In embodiments, the aesthetic modifier may include one or more colorants, such as dyes or pigments, and other aesthetic materials. Non-limiting examples of colorants include rhodamine, fluorescein, phthalocyanine, and aluminum oxide. In embodiments, the aesthetic modifier may include non-limiting examples of particles of different shapes and sizes, which may include one or more of epoxy-coated metallized polyethylene terephthalate aluminum, polyester beads, candelilla beads, silicates, and mixtures thereof.
[0181] In embodiments, the density modifier may include one or more of the following: glycerol, mannitol, sugar alcohols, inorganic salts, titanium dioxide; zinc oxide; iron oxide; cobalt oxide; nickel oxide; silver oxide; copper oxide; zirconium oxide; silicon dioxide; silver; zinc; iron; cobalt; nickel; copper;
[0182] In an embodiment, the water-soluble gelling agent may include one or more of lecithin, calcium alginate, agar, carrageenan, processed agar seaweed, locust bean gum, carob gum, guar gum, tragacanth gum, gum arabic, xanthan gum, karaya gum, tara gum, gellan gum, konjac, polysorbate, pectin, ammonium phosphate, sucrose acetate isobutyrate, glycerides of wood resins, cellulose, cellulose derivatives, and fatty acids.
[0183] In embodiments, the aqueous core may include an enzyme stabilizer. In embodiments, the enzyme stabilizer may include any conventional enzyme stabilizer, such as a water-soluble source of calcium and / or magnesium ions. In embodiments, the enzyme stabilizer may include one or more of a reversible protease inhibitor, such as boron compounds including borate esters, 4-formylphenylboronic acid, phenylboronic acid and their derivatives, compounds such as calcium formate, sodium formate and 1,2-propylene glycol, and diethylene glycol.
[0184] In an embodiment of the method of preparing a capsule having an aqueous core, the oil phase may comprise a precursor. The precursor may be as defined above.
[0185] In an embodiment, the precursor present in the oil phase can be present in an amount of about 1 wt % to about 50 wt % based on the total weight of the aqueous phase (which ultimately forms the core). Other suitable amounts include about 1 wt % to about 15 wt %, about 5 wt % to about 30 wt %, about 10 wt % to about 20 wt %, about 15 wt % to about 40 wt %, about 25 wt % to about 45 wt %, or about 15 wt % to about 50 wt % based on the total weight of the aqueous phase. For example, the oil phase may include about 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, or 50% by weight based on the total weight of the aqueous phase.
[0186] In embodiments of the method of preparing a capsule having an aqueous core, the nanoparticles may be present in one or both of the aqueous phase and the oil phase. In embodiments, the nanoparticles are present only in the aqueous phase. In embodiments, the nanoparticles are present only in the oil phase. In embodiments, the nanoparticles are present in both the oil phase and the aqueous phase.
[0187] Any of the above nanoparticles can be used in the water phase. In an embodiment, the nanoparticles can be present in a total amount of about 0.01% by weight to about 10% by weight based on the total weight of the water phase in one or both of the water phase and the oil phase. Other suitable amounts include about 0.05% by weight to about 5% by weight, about 1% by weight to about 10% by weight, about 5% by weight to about 8% by weight, about 2% by weight to about 7% by weight, or about 0.1% by weight to about 1% by weight. For example, the nanoparticles can be present in an amount of about 0.01 wt%, 0.02 wt%, 0.03 wt%, 0.04 wt%, 0.05 wt%, 0.06 wt%, 0.07 wt%, 0.08 wt%, 0.09 wt%, 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, or 10 wt% based on the total weight of the aqueous phase.
[0188] In embodiments, the method comprises blending the oil phase and the water phase in a ratio of about 10: 1 to about 1: 1, about 9: 1 to about 1: 1, about 5: 1 to about 1: 1, about 3: 1 to about 1: 1, about 5: 1 to about 2: 1, about 3: 1 to about 1.5: 1. Other suitable ratios include about 10: 1, 9: 1, 8: 1, 7: 1, 6: 1, 5: 1, 4: 1, 3: 1, 2: 1, 1.5: 1, or 1: 1.
[0189] Curing conditions
[0190] In embodiments, whether an oil-based core or an aqueous core is prepared, the emulsion may be cured under conditions that cure the precursor, thereby forming capsules.
[0191] In embodiments, the reaction temperature for curing may be increased in order to increase the rate at which cured capsules are obtained. The capsules are considered cured when they no longer collapse. The determination of capsule collapse is described in detail below.
[0192] In embodiments, during the curing step, hydrolysis of the Y moiety (from formula (I) and / or (II) occurs, followed by subsequent condensation of the -OH group with another -OH group or another moiety of the Y type (wherein the 2 Ys are not necessarily the same). The hydrolyzed precursor moieties will initially condense with the surface moieties of the nanoparticles (provided that they contain such moieties). As shell formation proceeds, the precursor moieties will react with the preformed shell.
[0193] In embodiments, the emulsion may be cured such that the shell precursor undergoes condensation. In embodiments, the emulsion may be cured such that the shell precursor reacts with the nanoparticles to undergo condensation. An example of the hydrolysis and condensation steps of the silica-based shell described herein is shown below:
[0194] Hydrolysis: ≡Si-OR+H2O→≡Si-OH+ROH
[0195] Condensation: ≡Si-OH+≡Si-OR→≡Si-O-Si≡+ROH
[0196] ≡Si-OH+≡Si-OH→≡Si-O-Si≡+H2O.
[0197] For example, in embodiments where a precursor of formula (I) or (II) is used, the hydrolysis and condensation steps are described below:
[0198] Hydrolysis: ≡M-Y+H2O→≡M-OH+YH
[0199] Condensation: ≡M-OH+≡MY→≡MOM≡+YH
[0200] ≡M-OH+≡M-OH→≡MOM≡+H2O.
[0201] Test Method
[0202] Average shell thickness measurement
[0203] The capsule shell, including the first shell component and the second shell component, when present, was measured in nanometers using a focused ion beam scanning electron microscope (FIB-SEM; FEI Helios Nanolab 650) or equivalent on a delivery capsule containing 20 of the beneficial agent. The sample was prepared by diluting a small amount of the liquid capsule dispersion (20 μl) with distilled water (1:10). The suspension was then deposited on an ethanol-cleaned aluminum rod and transferred to a carbon coater (Leica EM ACE600 or equivalent). The sample was vacuumed in the coater (vacuum level: 10 -5 The sample was dried at 1000 mbar. Next, 25 nm-50 nm of carbon was quickly deposited onto the sample to deposit a conductive carbon layer onto the surface. The aluminum rod was then transferred into a FIB-SEM to prepare a cross section of the capsule. Using the cross-section cleaning mode, cross sections were prepared by ion milling at 30 kV accelerating voltage with an emission current of 2.5 nA. Images were collected in immersion mode (dwell time of about 10 μs) at 5.0 kV and 100 pA with a magnification of about 10,000.
[0204] Images of the broken shells were collected in the form of cross-sectional views of 20 beneficial delivery capsules selected in a random manner without bias due to their size to form a representative sample presenting the distribution of capsule sizes. The shell thickness of each of the 20 capsules was measured at 3 different random locations by drawing a measurement line perpendicular to the tangent line to the outer surface of the capsule shell using the calibrated microscope software. 60 independent thickness measurements were recorded and used to calculate the average thickness.
[0205] Coefficient of variation of capsule diameter
[0206] The capsule size distribution was determined by single particle optical sensing (SPOS), also known as optical particle counting (OPC), using an AccuSizer 780AD instrument or equivalent and the accompanying software CW788 version 1.82 (Particle Sizing Systems, Santa Barbara, California, USA) or equivalent. The instrument was configured with the following conditions and options: flow rate = 1 mL / sec; lower size threshold = 0.50 μm; sensor model = LE400-05SE or equivalent; autodilution = on; collection time = 60 seconds; number of channels = 512; vascular fluid volume = 50 ml; maximum overlap = 9200. The measurement was started by flushing the sensor into a cold state with water until the background count was less than 100. The sample in the suspension of the delivery capsule was introduced and the density of the capsule was adjusted with DI water by autodilution as needed to obtain a capsule count of up to 9200 / mL. The suspension was analyzed over a period of 60 seconds. The size range used was 1 μm to 493.3 μm.
[0207] Volume distribution :
[0208]
[0209]
[0210]
[0211] in:
[0212] CoV v – Coefficient of variation of volume-weighted size distribution
[0213] σ v – Standard distribution deviation of volume distribution
[0214] μ v – Distribution mean of volume distribution
[0215] d i – diameter in fraction i
[0216] x i,v – The frequency in fraction i (corresponding to diameter i) of the volume distribution
[0217]
[0218] Nominal Wall Tension Method
[0219] Nominal wall tension T RThe following formula was used as described in "Liu, M. (2010). Understanding the mechanical strength of microcapsules and their adhesion on fabric surfaces. Birmingham, United Kingdom: University of Birmingham (Doctoral thesis)" to calculate
[0220]
[0221] Among them, F R is the rupture force of a single microcapsule, and D m is the diameter of a single capsule before compression. Nominal wall tension T R The diameter (D) of each capsule was measured by a computer-controlled micromanipulator system. m ) and rupture force value (F R ) (also known as the burst force value), the micromanipulation instrument system having a lens and camera capable of imaging the delivery capsule, and having a fine flat-end probe connected to a force sensor (such as Model 403A purchased from Aurora Scientific Inc. (Canada)) or equivalent, as described in the following literature: Zhang, Z. et al. (1999) "Mechanical strength of single microcapsules determined by a novel micromanipulation technique." J. Microencapsulation, Vol. 16, No. 1, pp. 117-124, and Sun, G. and Zhang, Z. (2001) "Mechanical Properties of Melamine-Formaldehyde microcapsules." J. Microencapsulation, Vol. 18, No. 5, pp. 593-602, and available from University of Birmingham (Edgbaston, Birmingham, UK).
[0222] The nominal wall tension is determined as follows :
[0223] a) Place a drop of the delivery capsule suspension on a glass microscope slide and dry for several minutes at ambient conditions to remove water and obtain a sparse monolayer of individual capsules on the dried slide. Adjust the concentration of capsules in the suspension as needed to obtain the appropriate capsule density on the slide. More than one slide preparation may be required.
[0224] b) The slide is then placed on the sample holding stage of the micromanipulator. Thirty benefit delivery capsules on the slide are selected for measurement so that ten capsules are selected within each of three predetermined size bands. Each size band refers to the capsule diameter derived from the volume-weighted PSD generated by the Accusizer. The three size bands for the capsules are: mean diameter + / - 2 μm; 5th percentile diameter + / - 2 μm; and 90th percentile diameter + / - 2 μm. Capsules that are deflated, leaking, or damaged are excluded from the selection process and are not measured.
[0225] c) For each of the 30 selected capsules, the diameter of the capsule is measured from the image on the micromanipulator and recorded. The same capsule is then compressed between two flat surfaces (i.e., a flat-ended force probe and a glass microscope slide) at a rate of 2 μm per second until the capsule breaks. During the compression step, the probe force is continuously measured and recorded by the data acquisition system of the micromanipulator instrument.
[0226] d) The diameter of each capsule (D m ) is measured using an experimental apparatus or equivalent and the method of Zhang, Z.; Sun, G: "Mechanical Properties of Melamine-Formaldehyde microcapsules." J. Microencapsulation, Vol. 18, No. 5, pp. 593-602, 2001.
[0227] e) Determine the rupture force (F) for each selected capsule based on the recorded force probe measurements R), as shown in the following documents: Zhang, Z. et al. (1999) "Mechanical strength of single microcapsules determined by a novel micromanipulation technique." J. Microencapsulation, Vol. 16, No. 1, pp. 117-124, and Sun, G. and Zhang, Z. (2001) "Mechanical Properties of Melamine-Formaldehyde microcapsules." J. Microencapsulation, Vol. 18, No. 5, pp. 593-602.
[0228] f) Nominal wall tension (T) of each of the 30 capsules R ) by dividing the rupture force (F R )(in Newtons) divided by the diameter of the capsule (D m ) is calculated by multiplying π, as described in “Liu, M. (2010). Understanding the mechanical strength of microcapsules and their adhesion on fabric surfaces. Birmingham, United Kingdom: University of Birmingham (Doctoral thesis)”.
[0229] Effective volume core-shell ratio evaluation
[0230] The effective volume core-shell ratio value is determined as follows, which depends on the average shell thickness as measured by the Shell Thickness Test Method. The effective volume core-shell ratio of a capsule whose average shell thickness is measured is calculated by the following formula:
[0231]
[0232] where thickness is the average shell thickness of the capsule population measured by FIBSEM, and D 胶囊 is the average volume-weighted diameter of the capsule population measured by optical particle counting.
[0233] This ratio can be converted to a core-shell ratio fraction by calculating the core weight percentage using the following formula:
[0234]
[0235] And the shell percentage can be calculated based on the following formula:
[0236] Shell % = 100 - core %.
[0237] Branching method
[0238] The degree of branching of the precursor was determined as follows: The degree of branching was measured using (29Si) nuclear magnetic resonance spectroscopy (NMR).
[0239] Sample preparation
[0240] Each sample was diluted to a 25% solution using deuterated benzene (Benzene-D6 "100%" (D, 99.96%, purchased from Cambridge Isotope Laboratories Inc., Tewksbury, MA, or equivalent). 0.015 M chromium (III) acetylacetonate (99.99% purity, purchased from Sigma-Aldrich, St. Louis, MO, or equivalent) was added as a paramagnetic relaxation reagent. If glass NMR tubes (Wilmed-Lab Glass, Vineland, NJ, or equivalent) were used for analysis, a blank sample must also be prepared by filling the NMR tube with the same type of deuterated solvent used to dissolve the sample. The same glass tube must be used to analyze the blank and the sample.
[0241] Sample analysis
[0242] The degree of branching is determined using a Bruker 400 MHz nuclear magnetic resonance spectroscopy (NMR) instrument or equivalent. Standard silicon (29Si) methods (e.g., from Bruker) are used with default parameters set to a minimum of 1000 scans and a relaxation time of 30 seconds.
[0243] Sample processing
[0244] Use system software such as MestReNova version 12.0.4-22023 (purchased from Mestrelab Research) or equivalent that is applicable to NMR spectrum to store and process samples.Application phase adjustment and background correction.There is a large wide signal extending from-70ppm to-136ppm, which is the result of using glass NMR tubes and the glass present in the probe shell.This signal is suppressed by subtracting the spectrum of blank sample from the spectrum of synthetic sample, and the prerequisite is to analyze blank and sample using the same pipe and the same method parameters.In order to further illustrate any slight differences in data collection, pipes, etc., the region outside the peak of the region of interest should be integrated and normalized to a consistent value.For example, for all blanks and samples, integration-117ppm to-115ppm and integral value is set to 4.
[0245] The resulting spectrum produces up to five major peak areas. The first peak (Q0) corresponds to unreacted TAOS. The second set of peaks (Q1) corresponds to the end groups. The next set of peaks (Q2) corresponds to linear groups. The next set of broad peaks (Q3) are semi-dendritic units. The last set of broad peaks (Q4) are dendritic units. When analyzing PAOS and PBOS, each group falls within a defined ppm range. Representative ranges are described in the following table:
[0246]
[0247]
[0248] Polymethoxysilane has different chemical shifts for Q0 and Q1, overlapping signals for Q2, and unchanged Q3 and Q4, as shown in the following table:
[0249] Group ID The number of bridging oxygen per silicon ppm range Q0 0 -78 to -80 Q1 1 -85 to -88 Q2 2 -91 to -96 Q3 3 -100 to -106 Q4 4 -108 to -115
[0250] The ppm ranges shown in the table above may not apply to all monomers. Other monomers may cause changes in the chemical shift, however, the correct assignment of Q0-Q4 should not be affected.
[0251] Using MestReNova, each set of peaks was integrated and the degree of branching was calculated by the following formula:
[0252]
[0253] Molecular weight and polydispersity index determination method
[0254] The molecular weight (polystyrene equivalent weight average molecular weight (Mw)) and polydispersity index (Mw / Mn) of the condensation layer precursors described herein are determined using size exclusion chromatography with refractive index detection. Mn is the number average molecular weight.
[0255] Sample preparation
[0256] The sample is weighed and then diluted to a target concentration of 10 mg / mL with the solvent used in the instrument system. For example, 50 mg of polyalkoxysilane is weighed into a 5 mL volumetric flask, dissolved and diluted to volume with toluene. After the sample has been dissolved in the solvent, it is passed through a 0.45 um nylon filter and loaded into the instrument autosampler.
[0257] Sample analysis
[0258] An HPLC system with an automatic sampler (e.g., Waters 2695 HPLC separation module, Waters Corporation, Milford MA, or equivalent) connected to a refractive index detector (e.g., Wyatt 2414 refractive index detector, Santa Barbara, CA, or equivalent) is used for polymer analysis. Separation is performed on three chromatographic columns, each 7.8 mm ID × 300 mm long, filled with 5 μm polystyrene-divinylbenzene media, connected in series, having molecular weight cutoffs of 1 kDA, 10 kDA, and 60 kDA, respectively. Suitable chromatographic columns are TSKGel G1000HHR, G2000HHR, and G3000HHR chromatographic columns (purchased from TOSOH Bioscience, King of Prussia, PA) or equivalent. A 6 mm ID × 40 mm long 5 μm polystyrene-divinylbenzene guard column (e.g., TSKgel Guardcolumn HHR-L, TOSOH Bioscience, or equivalent) is used to protect the analytical column. Toluene (HPLC grade or equivalent) was pumped isocratically at 1.0 mL / min while the column and detector were maintained at 25° C. 100 μL of the prepared sample was injected for analysis. Sample data was stored and processed using software with GPC calculation capabilities (e.g., ASTRA version 6.1.7.17 software, available from Wyatt Technologies, Santa Barbara, CA, or equivalent).
[0259] The system is calibrated using ten or more narrow dispersion polystyrene standards (e.g., the standard ReadyCal Set, (e.g., Sigma Aldrich, PN 76552, or equivalent)) with known molecular weights (in the range of about 0.250 kDa-70 kDa) and using a third order fit of the Mp versus retention time curve.
[0260] Using the system software, calculate and record the weight average molecular weight (Mw) and polydispersity index (Mw / Mn).
[0261] Beneficial Agent Permeation Test
[0262] The permeability test method allows the determination of the percentage of a specific molecule that diffuses from the capsule core of a population of capsules into the continuous phase, which can represent the permeability of the capsule shell. The permeability test method is a reference frame related to the shell permeability of a specific molecular tracer, thus fixing its size and its affinity for the continuous phase outside the capsule shell. This is a reference frame used to compare the permeability of various capsules in the art. When both the molecular tracer and the continuous phase are fixed, the shell permeability is a single capsule property evaluated under a specific set of conditions.
[0263] Capsule shell permeability is related to shell porosity, such that low permeability indicates low shell porosity.
[0264] Capsule permeability is usually given as a function of parameters such as shell thickness, concentration of active substance in the core, solubility of the active substance in the core, shell and continuous phase, etc.
[0265] In order for the active to diffuse through the shell, it must transfer from the core to the shell and then from the shell to the continuous phase. The latter step is rapid if the solubility of the active in the continuous phase is very favorable, which is the case for hydrophobic materials into a surfactant-based matrix. For example, an active present in the system at a level of 0.025 wt% is very likely to be completely soluble in 15 wt% surfactant.
[0266] In view of the above, the limiting step to minimize shell permeability of actives in surfactant-based matrices is to limit diffusion through the shell. In the case of hydrophobic shell materials, a hydrophobic active will readily dissolve in the shell if it is swellable by the active. This swellability may be limited by high shell crosslink density.
[0267] In the case of hydrophilic shell materials such as silica, the solubility of hydrophobic materials in the shell itself is limited. However, the active material is able to diffuse out quickly when the following factors are taken into account: surfactant molecules and micelles are able to diffuse into the shell and subsequently into the core itself, which allows a path from the core into the shell and ultimately into the external matrix.
[0268] Therefore, for hydrophilic shell materials, a high shell crosslink density is desired, but the number of pores within the shell is also reduced. Such pores can lead to rapid mass transfer of active substances into the surfactant-based matrix. Therefore, there is a clear and obvious correlation between the overall permeability of the capsule shell and its porosity. In fact, the permeability of the capsule gives insights into the overall shell structure of any given capsule.
[0269] As mentioned before, the diffusion of the active substance is defined by the nature of the active substance, its solubility in the continuous phase and the shell architecture (porosity, crosslink density and any general defects it may contain). Therefore, by fixing two of the three relevant parameters, we can actually compare the permeability of various shells.
[0270] The purpose of this permeability test is to provide a framework that allows a direct comparison of different capsule shells. Furthermore, it allows the properties of a large number of capsules to be evaluated and is therefore not affected by biased results obtained with outliers.
[0271] Thus, capsule permeability can be defined via the fraction of a given molecular tracer that diffuses into a given continuous phase under specific conditions within a given period of time (eg, 20% tracer diffusion within 7 days).
[0272] Capsules of the present invention will have a relative permeability of less than about 80%, less than about 70%, less than about 60%, less than about 50%, less than about 40%, less than about 30%, or less than about 20% as measured by the Permeability Test Method.
[0273] Permeability Test Method The molecular tracer tricyclodecenyl acetate (CAS# 5413-60-5) (Vigon) is measured for shell permeability of a capsule containing the tracer in the core relative to a reference sample representing complete diffusion of the tracer (eg, 100% permeability).
[0274] First, capsules are prepared according to any given capsule preparation method. For the purpose of the permeability test method, the capsule core must contain or be supplemented during preparation to contain at least 10% by weight of tricyclodecenyl acetate tracer by weight of the core. In this test, "weight of the core" refers to the weight of the core after the shell is formed and the capsule is prepared. The capsule core additionally contains its intended components, such as core modifiers and beneficial agents. The capsule can be prepared as a capsule slurry as commonly done in the art.
[0275] The capsules were then formulated into permeability test samples. The permeability test sample included mixing a sufficient amount of capsule slurry with an aqueous solution of sodium dodecyl sulfate (CAS#151-21-3) to obtain a total core oil content of 0.25 wt% ± 0.025 wt% and an SDS concentration of 15 wt% ± 1 wt% based on the total weight of the test sample. The amount of capsule slurry required can be calculated as follows:
[0276]
[0277] The oil activity of the slurry is the weight % of oil in the slurry as determined by mass balance of the capsule preparation process.
[0278] SDS solution can be prepared by dissolving SDS pellets in deionized water. Capsules and SDS solutions can be mixed under conditions designed to prevent capsules from breaking during mixing. For example, capsules and SDS solutions can be mixed together by hand or with an overhead mixer, but magnetic stirring bars should not be used for mixing. It has been found that mixing by magnetic stirring bars usually causes capsules to break. Suitable mixers may include an IKA propeller mixer that is no more than 400rpm, wherein the gross mass of the mixture comprising SDS solution and capsule slurry is 10g to 50g. Other suitable mixing devices and suitable conditions for mixing without using a magnetic stirring bar and without destroying a given capsule composition will be apparent to the technician.
[0279] After the permeability test sample is prepared, it is placed in a glass sample bottle with a total volume not exceeding twice the volume of the permeability test sample and sealed with an airtight cap. The sealed permeability test sample is stored at 35°C and 40% relative humidity for seven days. During storage, the sealed permeability test sample is not exposed to light and is not opened at any time point before measurement.
[0280] A reference sample representing 100% diffusion was also prepared. The reference sample was prepared on the day of measurement (i.e., seven days after the permeability test sample was prepared). The reference sample was prepared by mixing a free oil mixture with 15% by weight of aqueous SDS, the free oil mixture being intended to replicate the composition of the capsule core determined by the mass balance of the capsule prepared in the permeability test sample, including the core of the tricyclodecenyl acetate tracer of the same weight percentage. The free oil mixture and the SDS solution were homogenized with a magnetic stirrer until the free oil mixture was completely dissolved, and the container should be sealed during mixing to avoid tracer evaporation. If homogenization requires considerable time, this must be taken into account, and if necessary, reference material preparation can be started before the 7th day. Immediately after dissolution, the reference sample was placed in a glass sample bottle not exceeding twice the volume of the reference sample and sealed with an airtight lid. The SDS solution can be prepared by dissolving the SDS pellets in deionized water as in the permeability test sample.
[0281] The amount of free oil mixture is added to achieve a total concentration of free oil mixture in the reference sample of 0.25 wt % ± 0.025 % based on the total weight of the reference sample, as calculated by the following formula:
[0282]
[0283] The same GC / MS analysis equipment was used to analyze the permeability test sample (after seven days) and the reference sample on the same day as represented by the gas chromatography area count of tricyclodecenyl acetate. Specifically, for each test sample and reference sample, an aliquot of 100 μL of the sample was transferred to a 20 ml headspace sample bottle (Gerstel SPME sample bottle 20 ml, part number 093640-035-00) and immediately sealed (sealed with the Gerstel Crimp cover for SPME, part number 093640-050-00). Three headspace sample bottles were prepared for each sample. The sealed headspace sample bottles were then balanced. The sample reached equilibrium after 3 hours at room temperature, but can be left standing for a longer time without damaging or changing the result, until 24 hours after the sealed headspace sample bottle. After balance, the sample was analyzed by GC / MS.
[0284] GS / MS analysis was performed by sampling the headspace of each sample bottle via SPME (50 / 30 μm DVB / Carboxen / PDMS, Sigma-Aldrich part number 57329-U), with a sample bottle penetration of 25 mm and an extraction time of 1 minute at room temperature. The SPME fiber was then thermally desorbed online into the GC injector (270°C, splitless mode, 0.75 mm SPME inlet liner (Restek, part number 23434) or equivalent, 300 seconds desorption time and 43 mm injector penetration). Tricyclodecenyl acetate was analyzed by fast GC / MS in full scan mode. Tricyclodecenyl acetate (and isomers) headspace response (expressed in area counts) was calculated using ion extraction of the specific mass of tricyclodecenyl acetate (m / z=66). The headspace responses of the permeability test sample and the reference sample are referred to herein as the tricyclodecenyl acetate area counts of the permeability test sample and the tricyclodecenyl acetate area counts of the reference sample, respectively.
[0285] Suitable equipment for this method includes Agilent 7890B GC with 5977 MSD or equivalent, Gerstel MPS, SPME (autosampler), GC column: Agilent DB-5UI 30m x 0.25 x 0.25 column (Part No. 122-5532UI).
[0286] The analysis of the permeability test samples and the reference samples shall be performed on the same equipment, under the same room temperature conditions, and on the same day, one after the other.
[0287] Based on the actual known content of tricyclodecenyl acetate in the GC / MS data and permeability test samples, the permeability percentage can be calculated. The actual content of tricyclodecenyl acetate in the permeability test must be determined to correct any losses in the capsule preparation process. The method to be used is described in detail below. This takes into account the inefficiencies usually encountered when the product is encapsulated in the capsule core, and the tricyclodecenyl acetate less than the total expected amount present during the formation of the capsule present in the slurry (e.g., evaporation). The following formula can be used to calculate the permeability percentage.
[0288]
[0289] This calculated value is the % permeability of the tested capsules after storage for 7 days at 40% relative humidity and 35°C.
[0290] In order to evaluate the actual tricyclodecenyl acetate content in the SDS capsule mixture, an aliquot must be retrieved after the specified storage time. To this end, the resulting mixture is opened on the same day as the first sample is measured, thereby ensuring that the sample bottle remains sealed during storage. First, the mixture must be mixed until uniform in order to retrieve a representative aliquot containing the correct proportion of material. Then, 1 gram of the uniform mixture is introduced into a flat-bottomed glass sample bottle with a diameter of 1 cm, and a magnetic stirring bar with a length not less than half the diameter of the sample bottle is introduced into the sample bottle. The uniform mixture in the designated wide-mouth bottle equipped with a magnetic stirring bar is sealed, then placed on a magnetic stirring plate, and mixed using 500rpm so that the stirring action of the stirring bar grinds all capsules. This causes the encapsulated core material to be completely released into the surrounding SDS solution, thereby allowing the actual tricyclodecenyl acetate content to be measured. For unbroken capsules, the measurement scheme of the content must be performed. In addition, before the measurement step, the capsule must be observed under an optical microscope to assess whether all capsules have been broken. If not, the capsule grinding must be repeated, wherein the mixing speed and / or mixing time are increased.
[0291] Method for calculating the organic content in the first shell component
[0292] Definition of organic moiety in inorganic shell - any moiety X which cannot be cleaved from a metal precursor with a metal M (where M belongs to the group of metals and semimetals and X belongs to the group of nonmetals) via hydrolysis of the MX bond linking the moiety to the inorganic precursor of the metal or semimetal M under the specific reaction conditions will be considered organic. A minimum degree of hydrolysis of 1% was set as the reaction condition when exposed to neutral pH distilled water for a duration of 24 hours without stirring.
[0293] This method allows one to calculate the theoretical organic content assuming complete conversion of all hydrolyzable groups. Thus, it allows one to assess the theoretical organic percentage for any mixture of silanes, and the result represents only that precursor mixture itself, not the actual organic content in the first shell component. Thus, when a certain percentage of organic content for a first shell component is disclosed anywhere in this document, it should be understood that any mixture containing unhydrolyzed precursors or prepolymerized precursors will have a theoretical organic content according to the following calculation that is lower than the disclosed amount.
[0294] Examples of silanes (but not limited to silanes, see the general formula at the end of the document):
[0295] Consider a mixture of silanes, where the mole fraction of each is Y i , and wherein i is the ID number of each silane. The mixture can be represented as follows:
[0296] Si(XR) 4-n R n
[0297] Where XR is a hydrolyzable group under the conditions mentioned in the above definition, R i ni It is not hydrolyzable under the above conditions, and n i =0, 1, 2 or 3.
[0298] This silane mixture will produce a shell with the following general formula:
[0299]
[0300] Then, the weight percent of the organic portion as previously defined can be calculated as follows:
[0301] 1) Find the mole fraction of each precursor (including nanoparticles)
[0302] 2) Determine the general formula of each precursor (including nanoparticles)
[0303] 3) General formula for calculating the mixture of precursor and nanoparticles based on mole fractions
[0304] 4) Converted into reactive silane (all hydrolyzable groups are converted into oxygen groups)
[0305] 5) Calculate the weight ratio of the organic part relative to the total mass (assuming the framework is 1 mol Si)
[0306] Example
[0307]
[0308] To calculate the general formula for a mixture, each atomic index in the individual chemical formulas is multiplied by their respective mole fractions. Then, for mixtures, when similar indices occur (usually for ethoxy groups), the sum of the fractional indices is taken.
[0309] Note: Due to the calculation method (the sum of all mole fractions of Si is 1), the sum of all Si fractions in the mixture formula will always add to 1.
[0310] SiO 1*0.57+2*0.25 (OEt) 2*0.57+4*0.07+2*0.10 Me 2*0.10
[0311] SiO 1.07 (OEt) 1.62 Me 0.20
[0312] To convert the unreacted formula to the reacted formula, simply divide the indices of all hydrolyzable groups by 2 and then add them together (along with any pre-existing oxygen groups, if applicable) to obtain the fully reacted silane.
[0313] SiO 1.88 Me 0.20
[0314] In this case, the expected result is SiO 1.9 Me 0.2 , because the sum of all exponents must satisfy the following formula:
[0315] A+B / 2=2,
[0316] Where A is the oxygen atom index and B is the sum of all non-hydrolyzable indices. Small errors may occur during calculation due to rounding and should be corrected. The indices on the oxygen atoms are then readjusted to satisfy the formula.
[0317] Therefore, the final chemical formula is SiO 1.9 Me 0.2 , and the weight ratio of organic matter is calculated as follows:
[0318] Weight ratio: =(0.20*15) / (28+1.9*16+0.20*15)=4.9%
[0319] General:
[0320] The above formula can be generalized by taking into account the valence of the metal or semimetal M, giving the following modified formula:
[0321] M(XR) V-m R i m
[0322] And a similar approach is used, but the valence V of the corresponding metal is taken into account.
[0323] Example
[0324] Although specific embodiments of the present disclosure have been illustrated and described, it will be apparent to those skilled in the art that various other changes and modifications may be made without departing from the spirit and scope of the present disclosure. Therefore, it is intended that all such changes and modifications within the scope of the present disclosure be covered in the appended claims.
[0325] Example 1: Non-hydrolyzable precursor synthesis
[0326] The precursors of samples AS and AV-AAD were prepared by the following method:
[0327] Under nitrogen atmosphere, a certain amount of TAOS reagent (purchased from Sigma Aldrich) is added in the clean dry round-bottomed flask equipped with stirring rod and distilling equipment.Add certain volume of diacetyl oxide (purchased from Sigma Aldrich) and catalyzer (purchased from Gelest, Sigma Aldrich), and stir and heat the content of flask, as shown in table 1.Reaction is heated to indicated temperature and keeps indicated time, during this period, distill out the organic ester generated by the reaction of alkoxysilane group and diacetyl oxide and the other organic ester generated by the condensation of silyl acetate group and other alkoxysilane groups, this condensation occurs when generating polyalkoxysilane (PAOS).Reaction flask is cooled to room temperature and is placed on the rotary evaporator (Buchi Rotovapor R110) used in combination with water-bath and vacuum pump (Welch 1402DuoSeal), to remove any residual solvent.All reactants and reagent types and ratio, catalyzer and ratio and all reaction conditions (such as time and temperature) are detailed in table 1.
[0328] The following reactants may be abbreviated as follows: tetraethoxysilane (TEOS), tetramethoxysilane (TMOS), tetrabutoxysilane (TBOS), triethoxymethylsilane (TEMS), diethoxy-dimethylsilane (DEDMS), trimethylethoxysilane (TMES), tetraacetoxysilane (TAcS), and titanium tetrabutoxide (TTB).
[0329] Example 2: Hydrolysis Precursor Synthesis
[0330] The precursors of samples UZ, AA-AI and AK-AAB were prepared by the following method:
[0331] Under nitrogen atmosphere, a certain amount of TAOS reagent (purchased from Sigma Aldrich) is added in the clean dry round-bottomed flask equipped with stirring rod and distillation equipment, and a certain amount of alcohol (purchased from Sigma Aldrich) is added thereto. As shown in Table 2, a certain amount of catalyst dissolved in water is added. 1N and 0.1N HCl dissolved in water are purchased from SigmaAldrich. 0.002N HCl is prepared by diluting 0.1N HCl in distilled water (purchased from Sigma Aldrich). Reaction is stirred and heated to the indicated temperature for the duration of the indicated time, during which time, the alcohol generated by the hydrolysis of alkoxysilane group and alcohol solvent and some water generated by the condensation of silanol groups are distilled out, and this condensation occurs when generating polyalkoxysilane (PAOS). The reaction flask is cooled to room temperature and placed on the rotary evaporator (Buchi Rotovapor R110) used in combination with a water-bath and a vacuum pump (Welch 1402DuoSeal), to remove any residual solvent. All reactant and reagent types and ratios, catalysts and ratios, and all reaction conditions (eg, time and temperature) are detailed in Table 2.
[0332] In some samples (such as samples AB and AC), further reactions are required, as shown in step 2 of Table 2 below. In step 2, the procedure described above is repeated, except that the product from the above reaction is used as the starting material. All reactant and reagent types and ratios, catalysts and ratios, and all reaction conditions (e.g., time and temperature) are detailed in Table 2.
[0333]
[0334]
[0335]
[0336]
[0337]
[0338]
[0339] Example 3: Oil-in-water capsules
[0340] The capsules of Part A of Table 3 (Samples C, E, F, G, H, I, J, K, L, Q, S, T, Z, AA, AB, AC, and Comparative Example W) were prepared by the following method:
[0341] The oil phase is prepared by mixing and homogenizing (or even dissolving, if all compounds are miscible) the precursors with the beneficial agent and / or core modulator. The aqueous phase is prepared by adding an acid or base to water to produce the desired starting pH. Next, the nanoparticles are added to the aqueous phase and dispersed using an ultrasonic bath for at least 30 minutes.
[0342] Once each phase is prepared separately, they are combined and the oil phase is dispersed into the water phase with appropriate mixing tools, time and energy to achieve the desired average capsule diameter for the capsules. If not otherwise specified, once the emulsification step is completed, the resulting emulsion is left to stand without stirring at a specific temperature until sufficient solidification occurs so that the capsules do not collapse. Optionally, the capsules may receive a post-treatment of a second shell component solution in order to deposit the second shell component, the materials and amounts being described in Table 3.
[0343] To test whether the capsules collapse, the slurry must be diluted at least 10 times in deionized water. Several drops of subsequent dilutions are added to a microscope slide and allowed to dry overnight at room temperature. The next day, the dried capsules are observed under an optical microscope through light to assess whether the capsules retain their spherical shape (without using a cover glass).
[0344] All reagent types and ratios and all reaction conditions (eg, mixing, curing time, and temperature) are detailed in Table 3, and the results are detailed in Table 4. All results were tested or measured according to the test methods described herein.
[0345] Figure 2A The capsules of Sample Q of Tables 3 and 4 are shown, and Figure 2B The capsule shell of Sample Q is shown. Figure 3A The unbroken capsules of Sample 1 of Tables 3 and 4 are shown, Figure 3B The capsule shell of Sample 1 is shown. Figure 4A The capsules of Sample E of Tables 3 and 4 are shown, and Figure 4B The capsule shell of Sample E is shown. Figure 5 Capsules of Sample C of Tables 3 and 4 are shown. Figure 6 The capsule shells of Sample Z of Tables 3 and 4 are shown. FIG. 7A to FIG. 7B Capsules having a substantially inorganic shell comprising a first shell component and a second shell component of Sample G of Tables 3 and 4 are shown. Fig. 8A The capsules of Tables 3 and 4 having a substantially inorganic shell comprising a first shell component and a second shell component of Sample H are shown, and Figure 8B A capsule having a substantially inorganic shell comprising a first shell component and a second shell component of Sample H is shown, and Fig. 9 The collapsed capsule shells of Sample W of Tables 3 and 4 are shown. Fig.10The energy dispersive X-ray spectra of the capsules of sample K of Tables 3 and 4 are shown, and Fig.11 The energy dispersive X-ray spectrum of the capsule of sample AA is shown.
[0346] Example 4: Water-in-oil capsule
[0347] The capsules of Part A of Table 3 (Examples N and AD) were prepared by the following method:
[0348] The aqueous phase is prepared by mixing and homogenizing any combination of the following: water, core modifier, beneficial agent and nanoparticles with at least one beneficial agent. The oil phase consists of a large excess of a hydrophobic liquid as a continuous phase. The oil phase can be a solvent or any liquid organic molecule that is substantially immiscible with water. The oil phase contains nanoparticles that are fully dispersed in the above-mentioned hydrophobic liquid in an ultrasonic bath for at least 30 minutes. The continuous oil phase includes a metal oxide precursor before or after emulsification, and an organic acid before or after emulsification.
[0349] Once each phase is prepared separately, they are combined and the aqueous phase is dispersed into the oil phase with appropriate mixing tools, time and energy to achieve the desired average diameter of the capsules. If not otherwise specified, once the emulsification step is completed, the resulting emulsion is left to stand without stirring at a specific temperature until sufficient solidification occurs so that the capsules do not collapse. Optionally, the capsules can receive a post-treatment of a second shell component solution in order to deposit the second shell component, the materials and amounts are described in Table 3.
[0350] To test whether the capsules collapse, the slurry must be diluted at least 10 times in deionized water. Several drops of subsequent dilutions are added to a microscope slide and allowed to dry overnight at room temperature. The next day, the dried capsules are observed under an optical microscope through light to assess whether the capsules retain their spherical shape (without using a cover glass).
[0351] All reagent types and ratios and all reaction conditions (eg, mixing, curing time, and temperature) are detailed in Table 3, and the results are detailed in Table 4. All results were tested or measured according to the test methods described herein.
[0352] Fig. 12A and Fig. 12B Capsules of Sample N of Tables 3 and 4 are shown.
[0353] Example 5: Oil-in-water capsules with variable shell organic percentage
[0354] The capsules of Part B of Table 3 (Examples AF, AH, AJ and Comparative Examples AE, AG, AK, AL, AI, AM, AN, AO, AP) were prepared by the following method:
[0355] The oil phase is prepared by mixing and homogenizing (or even dissolving, if all compounds are miscible) the precursors with the beneficial agent and / or core modulator. The aqueous phase is prepared by adding an acid or base to water to produce the desired starting pH. Next, the nanoparticles are added to the aqueous phase and dispersed using an ultrasonic bath for at least 30 minutes.
[0356] Once each phase is prepared separately, they are combined and the oil phase is dispersed into the water phase with appropriate mixing tools, time and energy to achieve the desired average capsule diameter for the capsules. If not otherwise specified, once the emulsification step is completed, the resulting emulsion is left to stand without stirring at a specific temperature until sufficient solidification occurs so that the capsules do not collapse. Optionally, the capsules may receive a post-treatment of a second shell component solution in order to deposit the second shell component, the materials and amounts being described in Table 3.
[0357] To test whether the capsules collapse, the slurry must be diluted at least 10 times in deionized water. Several drops of subsequent dilutions are added to a microscope slide and allowed to dry overnight at room temperature. The next day, the dried capsules are observed under an optical microscope through light to assess whether the capsules retain their spherical shape (without using a cover glass).
[0358] All reagent types and ratios and all reaction conditions (eg, mixing, curing time, and temperature) are detailed in Table 3, and the results are detailed in Table 4. All results were tested or measured according to the test methods described herein.
[0359] Part B of Tables 3 and 4 (capsule preparation and results, respectively) show that capsules with increased percentage of organic content in the first shell component have increased permeability after adding the second shell component, such as Fig.13 With only the first shell member, the permeability is high, but the capsule can resist drying out without collapsing.
[0360] Example 6: Oil-in-water capsules with variable core / shell ratio values
[0361] The capsules of Part C of Table 3 (Examples AU, AV and Comparative Examples B, AQ, AR, AS, AT, AW) were prepared by the following method:
[0362] The oil phase is prepared by mixing and homogenizing (or even dissolving, if all compounds are miscible) the precursors with the beneficial agent and / or core modulator. The aqueous phase is prepared by adding an acid or base to water to produce the desired starting pH. Next, the nanoparticles are added to the aqueous phase and dispersed using an ultrasonic bath for at least 30 minutes.
[0363] Once each phase is prepared separately, they are combined and the oil phase is dispersed into the water phase with appropriate mixing tools, time and energy to achieve the desired average capsule diameter for the capsules. If not otherwise specified, once the emulsification step is completed, the resulting emulsion is left to stand without stirring at a specific temperature until sufficient solidification occurs so that the capsules do not collapse. Optionally, the capsules may receive a post-treatment of a second shell component solution in order to deposit the second shell component, the materials and amounts being described in Table 3.
[0364] To test whether the capsules collapse, the slurry must be diluted at least 10 times in deionized water. Several drops of subsequent dilutions are added to a microscope slide and allowed to dry overnight at room temperature. The next day, the dried capsules are observed under an optical microscope through light to assess whether the capsules retain their spherical shape (without using a cover glass).
[0365] All reagent types and ratios and all reaction conditions (eg, mixing, curing time, and temperature) are detailed in Table 3, and the results are detailed in Table 4. All results were tested or measured according to the test methods described herein.
[0366] The examples in Table 3, Part C demonstrate the importance of combining the disclosed optimal average volume-weighted capsule diameter (10 um-200 um), average shell thickness (170 nm-1000 nm), and core-shell ratio (80:20-98:2) to obtain low shell permeability according to the Shell Permeability Method. Fig.14 The regions of interest when plotting the Examples (permeability < 40%) and Comparative Examples (permeability > 40%) are shown. Fig.15A The capsule shell of Sample B (Comparative Example) having a core-shell ratio of 78:22 of Tables 3 and 4 is shown, and Fig. 15B The capsule of sample B is shown. Fig.16 Capsule shells of samples AW (comparative examples) of Tables 3 and 4 having a core-shell ratio of 99:1 are shown.
[0367] Example 7: Oil-in-water capsules prepared with variable first shell component precursor branching degree and molecular weight
[0368] The capsules of Part D of Table 3 (Examples AAA, AAB, AAC and Comparative Examples AX, AY, AAD, AAE, AAF) were prepared by the following method:
[0369] The oil phase is prepared by mixing and homogenizing (or even dissolving, if all compounds are miscible) the precursors with the beneficial agent and / or core modulator. The aqueous phase is prepared by adding an acid or base to water to produce the desired starting pH. Next, the nanoparticles are added to the aqueous phase and dispersed using an ultrasonic bath for at least 30 minutes.
[0370] Once each phase is prepared separately, they are combined and the oil phase is dispersed into the water phase with appropriate mixing tools, time and energy to achieve the desired average capsule diameter for the capsules. If not otherwise specified, once the emulsification step is completed, the resulting emulsion is left to stand without stirring at a specific temperature until sufficient solidification occurs so that the capsules do not collapse. Optionally, the capsules may receive a post-treatment of a second shell component solution in order to deposit the second shell component, the materials and amounts being described in Table 3.
[0371] To test whether the capsules collapse, the slurry must be diluted at least 10 times in deionized water. Several drops of subsequent dilutions are added to a microscope slide and allowed to dry overnight at room temperature. The next day, the dried capsules are observed under an optical microscope through light to assess whether the capsules retain their spherical shape (without using a cover glass).
[0372] All reagent types and ratios and all reaction conditions (eg, mixing, curing time, and temperature) are detailed in Table 3, and the results are detailed in Table 4. All results were tested or measured according to the test methods described herein.
[0373] The capsule data in Table 3, Part D, show that capsules prepared with PAOS having a branching degree of less than 0.2 and a molecular weight of less than 700 Da exhibited a shell permeability of greater than 40% and / or did not resist air drying without collapse, as shown in FIG. Fig.17 As shown in the figure.
[0374] By way of example, the following is a detailed description of the application of the Permeability Test Method to determine the shell permeability of the capsules of Example R in Tables 3 and 4 below.
[0375] Tricyclodecenyl acetate was present in the fragrance composition at a level of 13% by weight.
[0376] Based on the mass balance of the capsule preparation protocol, the capsule slurry obtained from Example R of Table 3 has an oil activity of 19.04%. 0.131 g of this slurry was weighed into 9.87 g of a 15 wt % SDS (water) solution to obtain a product with an oil concentration of 0.249 wt % and an SDS concentration of 14.53%. The resulting mixture was fully dispersed by gently shaking the sample bottle in a circular motion by hand. The glass sample bottle was hermetically sealed with an airtight cap and stored at 35 degrees Celsius and 40% humidity for 7 days. The day of product preparation was considered to be day 0. It was found that the actual tricyclodecenyl acetate content in the sample corresponded to the theoretical value.
[0377] On day 7, 0.126 g of the oil used to prepare the capsules was weighed into 49.88 g of a 15 wt% SDS (water) solution to obtain a reference sample having an oil concentration of 0.252% and an SDS concentration of 14.96%. The resulting mixture was stirred in a sealed jar with the aid of a magnetic stirrer until the oil was completely dissolved. The reference sample was set aside and stored at room temperature.
[0378] Prior to measurement, the product containing the capsules was removed from the storage device. The capsules had settled to the bottom of the sample bottle. The capsules were redispersed by gently shaking the sample bottle in a circular motion until the entire volume of liquid was turbid. Immediately after the capsules were redispersed, a 100 μL aliquot was inserted into the bottom of 3 separate headspace sample bottles using a positive displacement pipette (obtained from Eppendorf) and immediately sealed with a crimp cap.
[0379] The same operation was performed for the reference product.
[0380] After equilibration at room temperature for 3 hours, the first replicate of the sample vial containing the reference product was measured via headspace GC / MS as described in the Test Methods section. Once the GC oven had cooled to the starting temperature, the next replicate was measured immediately, and so on, until all replicates of the reference and the product containing the capsules had been analyzed.
[0381] The ion chromatogram with M / Z 66 was extracted, and the peaks corresponding to tricyclodecenyl acetate and its isomers were identified by reading the full mass spectrum and comparing with the literature. These identified peaks were then integrated to obtain the area under the peak. The average of the areas of 3 replicates of the reference sample and the capsule sample was obtained (Table A below):
[0382] Table A
[0383]
[0384] Based on the above table, the average area of the reference sample was 73233, and the average area of the product containing capsules was 49731.
[0385] Shell permeability of tricyclodecenyl acetate after storage for 7 days at 35 degrees Celsius and 40% relative humidity.
[0386]
[0387]
[0388]
[0389]
[0390]
[0391] The conditions cited in Table 3
[0392] a. Menthyl lactate (MML) was prepared by mixing menthol and menthyl lactate in a 1:1 weight ratio, which yields a liquid at room temperature (U.S. Pat. No. 6,897,195 B2 discloses how to prepare such a mixture, the disclosure of which is incorporated herein by reference).
[0393] b. Cured at room temperature for 4 hours, at 50°C for 16 hours, and at 70°C for 96 hours
[0394] c. Curing at 50℃ for 3 weeks
[0395] d. Curing at room temperature for more than 5 weeks
[0396] e. The slurry was diluted 20 times in 0.1 HCl and treated with the second shell component precursor solution, which was added dropwise using a plastic pipette at room temperature and pH 1.2 with constant stirring at 350 RPM using an overhead stirrer. The capsules were kept under stirring at 300 RPM for 24 hours, then centrifuged at 2500 rpm for 10 minutes and redispersed in DI water.
[0397] f. The slurry was diluted 4 times in 0.1 HCl and treated with a second shell component precursor solution at 350 RPM controlled addition (10 μl / min) at room temperature using a hanging magnetic stirrer reactor. The pH was kept constant at pH 7 using 1 M HCl (water) and 1 M NaOH (water) solutions. The capsules were kept under 300 RPM stirring for 24 hours, then centrifuged at 2500 rpm for 10 minutes and redispersed in DI water.
[0398] g. The slurry was diluted 10 times in deionized water and treated with controlled addition of CaCl2 aqueous solution (1M, 1 ml) and Na2CO3 (1M, 1 ml) at 350 RPM over 1 hour using a suspended magnetic stirrer reactor. The pH was kept constant at pH 7 using 1M HCl (aq) and 1M NaOH (aq) solutions. The capsules were kept under stirring at 300 RPM for 24 hours, then centrifuged at 2500 rpm for 10 minutes and redispersed in DI water.
[0399] h. Before each step and after step (3), the slurry must be washed with 10 g of DI water, centrifuged at 1500 rpm for 10 minutes and the supernatant separated 3 times. The slurries from steps (1) and (2) are added to the solution and the mixture is shaken at room temperature for 10 minutes using a laboratory shaker. The slurry from step (3) is added to the solution and shaken at 150 rpm for 1 hour at 60°C using an overhead mixer.
[0400]
[0401]
[0402] For all of the following examples, the capsules were tested for collapse using the following method: 0.1 g of the slurry was diluted into 5 g of DI water. A few drops of this dilution were added to a microscope slide and the capsules were air dried until all the water evaporated. When the dried slurry was observed with an optical microscope, it was determined that the capsules did not collapse if they retained their initial spherical shape.
[0403] The following Example 8-1 and Comparative Examples 8-2 and 8-3 illustrate the importance of using a precursor as disclosed herein in combination with nanoparticles and a second shell component as disclosed herein to obtain low shell permeability.
[0404] Example 8-1
[0405] An aqueous phase was prepared by weighing 1.25 g Aerosil 300 and adjusting the total weight to 100 g with 0.1 M HCl. The nanoparticles were dispersed by sonicating the mixture in an ultrasonic bath for at least 30 minutes or until no more solid precipitates.
[0406] An oil phase was prepared by mixing 1 g of Precursor AY with 4 g of a fragrance mixture of formula A and homogenizing (see below).
[0407] 16 g of the aqueous phase were mixed with the above oil phase using an ultraturrax (S25N-10 g mixing tool from IKA) at 13500 rpm for 1 minute. The resulting mixture was covered with an airtight lid and allowed to stand at room temperature for 4 hours and at 50°C for another 3 weeks.
[0408] After 3 weeks at 50°C, a capsule slurry formed. The capsules did not collapse on a microscope slide.
[0409] The slurry was diluted 4-fold in 0.1 HCl and treated with 2 g of 10 wt % sodium silicate (aqueous solution) at 350 RPM with controlled addition (10 μl / min) at room temperature using a hanging magnetic stirrer reactor. The pH was kept constant at pH 7 using 1 M HCl (aqueous) and 1 M NaOH (aqueous) solutions. The capsules were kept under stirring at 300 RPM for 24 hours, then centrifuged at 2500 rpm for 10 minutes and redispersed in DI water.
[0410] The resulting capsule slurry was subjected to a permeability test as disclosed herein, and the shell permeability % based on the permeability test was 21%.
[0411] Comparative Example 8-2
[0412] The aqueous phase was prepared by diluting a 25 wt % CTAC (aq) solution (supplied by Sigma Aldrich) in DI water to achieve a CTAC concentration of 0.52 wt %.
[0413] An oil phase was prepared by mixing 40 g of fragrance of formula (A) and 10 g of TEOS.
[0414] The oil phase was mixed with 100 g of the aqueous phase at 8500 rpm using an ultraturrax mixer (S25N mixing tool from IKA) for 1 minute. The pH of the resulting emulsion was adjusted to 3.9 using 1 M NaOH (provided by Sigma Aldrich). The emulsion was then stirred continuously at 160 rpm with an overhead stirrer and heated at 30 ° C for 17 hours in a jacketed reactor covered to avoid evaporation of water or any other component. After 17 hours of reaction time, capsules were formed. The capsules collapsed when air-dried.
[0415] The resulting capsule slurry was subjected to the Permeability Test as disclosed herein, and based on the Permeability Test, the Shell Permeability % was 67%.
[0416] Comparative Example 8-3
[0417] Same as Comparative Example 8-1, except that after the capsule slurry was formed, the pH was adjusted to 3.2, and 5.7 g of TEOS was added dropwise over 320 minutes while the temperature was maintained at 30° C. with an overhead stirrer and the mixing rate was maintained at 160 rpm. After all the TEOS was added, the slurry was mixed for another 18 hours at 30° C. and 160 rpm with an overhead stirrer to obtain capsules. The capsules did not collapse when air-dried.
[0418] The resulting capsule slurry was subjected to the Permeability Test as disclosed herein, and based on the Permeability Test, the Shell Permeability % was 67%.
[0419] Fragrance formula (A) :
[0420] Hexyl acetate 9 wt%
[0421] Methyl dihydrojasmonate 9 wt%
[0422] Tetrahydrolinalool 9 wt%
[0423] α-ionone 9 wt%
[0424] Lilial 18 wt%
[0425] Hexylcinnamaldehyde 18 wt%
[0426] Hexyl salicylate 18 wt%
[0427] Tricyclodecenyl acetate 10 wt%
[0428] The following Example 9-1 and Comparative Examples 9-2 and 9-3 illustrate the importance of using a precursor as disclosed herein in combination with nanoparticles and a second shell component as disclosed herein to obtain low shell permeability.
[0429] Example 9-1
[0430] Example ID AAA from Table 3. The capsule did not collapse when air dried and had a % Permeability of 20% in the Permeability Test.
[0431] Comparative Example 9-2 :
[0432] In a 50 ml round bottom flask equipped with a magnetic stir bar, 4 g of 0.01 M HCl (aqueous solution) was mixed with 3 g of phenyltriethoxysilane (PhTEOS). Initially, the two phases were immiscible. Next, the mixture was stirred vigorously at 1000 rpm while adjusting the pH to 2 with 0.1 M NaOH. The mixture was stirred at 1000 rpm and room temperature until a homogeneous mixture was obtained. This gave a precursor mixture.
[0433] Next, 1.5 g of the same fragrance as, for example, AAA was added to 48.5 g of water containing 18 mg of a 50% by weight CTAC solution. The resulting mixture was stirred at room temperature for 30 minutes with a magnetic stirring bar, after which 2.5 ml of 25% by weight ammonia and 5 ml of the precursor mixture prepared above were added. This was stirred for another 2 hours, after which capsules were formed. The capsules collapsed after air drying.
[0434] Based on the permeability test, the capsules have a permeability % of 99%.
[0435] Comparative Example 9-3
[0436] Weigh 144 g of the same fragrance as, for example, AAA in a container. In a separate container, produce 96 g of a 1 wt % CTAC solution by mixing 3.84 g of a 25 wt % CTAC solution with DI water and adjusting the mass to 96 g. Mix the fragrance with the surfactant mixture using an IK Austraturrax mixer (S25N mixing tool) at 8000 rpm for 5 minutes.
[0437] Next, 144 g of water with a pH of 3.8 (adjusted with concentrated HCl) was added to the emulsion system prepared above.
[0438] Next, 27 g of a mixture containing 26.73 g TEOS and 0.27 g dimethyldiethoxysilane was added dropwise to the emulsion system under constant mixing. When all precursors were added, the mixture was heated to 50° C. and stirred at 200 rpm in a jacketed reactor with an overhead mixer for 2 hours.
[0439] The resulting capsules collapsed when air dried and had a % Permeability of 77% as determined by the Permeability Test.
[0440] The following Examples 10-1 and 10-3 and Comparative Examples 10-2, 10-4, 10-5 and 10-6 illustrate the importance of selecting appropriate precursors, nanoparticles and second shell components as disclosed in the present invention to obtain capsules with low permeability.
[0441] Example 10-1
[0442] An aqueous phase was prepared by weighing 1.25 g Aerosil 300 and adjusting the total weight to 100 g with 0.1 M HCl. The nanoparticles were dispersed by sonicating the mixture in an ultrasonic bath for at least 30 minutes or until no more solid precipitates.
[0443] An oil phase was prepared by mixing 1 g of Precursor AY with 3.5 g of isopropyl myristate and 0.5 g of tricyclodecenyl acetate and homogenizing.
[0444] 16 g of the above aqueous phase was mixed with the above oil phase using an ultraturrax (S25N-10 g mixing tool from IKA) at 13500 rpm for 1 minute. The resulting mixture was covered with an airtight lid and allowed to stand at room temperature for 4 hours and at 50°C for another 3 weeks.
[0445] After 3 weeks at 50°C, a capsule slurry was formed. The capsule did not collapse on a microscope slide. The capsule had no second shell component added, and based on the permeability test, the capsule permeability % was 40%.
[0446] Comparative Example 10-2
[0447] Same process as ID AAC of Table 3, for example, except that the second shell component was not added. The capsules remained after drying, and based on the permeability test, the capsule permeability % was 98%.
[0448] Example 10-3
[0449] Example ID AAC from Table 3. The capsules remained after drying and based on the permeability test, the capsule permeability % was 25%.
[0450] Comparative Example 10-4
[0451] An oil phase was prepared by mixing 20 g TEOS, 115 g isopropyl myristate and 15 g tricyclodecenyl acetate.
[0452] Next, an aqueous phase was prepared by weighing 10 g of a 25 wt % CTAC (aq) solution and adjusting the weight to 150 g with DI water to achieve a CTAC concentration of 1.67 wt %.
[0453] The two phases were mixed together for 1 minute at 6000 rpm using an Ultraturrax mixer (S25N tool from IKA). Next, 50 g of Ludox TM50 were added and the system was further mixed for another 1 minute at 8000 rpm. Next, the pH was adjusted to 5 with 1 M HCl.
[0454] To the above mixture was added 50 g of a 10 wt % PVOH aqueous solution (selvol 540) and 5 g of a 25 wt % sodium silicate aqueous solution. The pH was then readjusted to 4 and the system was stirred at 200 rpm for 20 hours at room temperature with an overhead mixer. The capsules collapsed when air-dried on a microscope slide and based on the permeability test, the capsule permeability % was 92%.
[0455] Comparative Example 10-5
[0456] Same as Comparative Example 10-4, except that 40 g of a 5 wt% aqueous solution of polyquaternium-7 was further added at the end after capsule formation. The capsules collapsed when air-dried on a microscope slide, and based on the permeability test, the capsule permeability % was 83%.
[0457] Comparative Example 10-6
[0458] The same method as in Comparative Example 10-2 above, except that 1.3 g of a 5% by weight aqueous solution of polyquaternium-7 was further added to 5 g of the slurry, and the mixture was stirred for 15 minutes at 200 rpm with an overhead stirrer. The capsules remained after drying, and based on the permeability test, the capsule permeability % was 73%.
[0459] The dimensions and values disclosed herein are not to be understood as being strictly limited to the exact numerical values cited. Instead, unless otherwise indicated, each such dimension is intended to represent the stated value and a functionally equivalent range around that value. For example, a dimension disclosed as "40 mm" is intended to mean "about 40 mm".
[0460] Unless expressly excluded or otherwise limited, each document cited herein, including any cross-referenced or related patent or patent application and any patent application or patent to which this application claims priority or the benefit of, is hereby incorporated by reference in its entirety. The citation of any document is not an admission that it is prior art to any of the present invention disclosed or claimed herein, or an admission that it, by itself or in combination with any one or more of the references, proposes, suggests, or discloses any such invention. In addition, to the extent that any meaning or definition of a term in this invention conflicts with any meaning or definition of the same term in a document incorporated by reference, the meaning or definition assigned to that term in this invention shall govern.
[0461] Although specific embodiments of the present invention have been illustrated and described, it will be apparent to those skilled in the art that various other changes and modifications may be made without departing from the spirit and scope of the present invention. Therefore, it is intended that all such changes and modifications within the scope of the present invention be covered in the appended claims.
Claims
1. A capsule, comprising: an oil-based core comprising a benefit agent; and a shell surrounding the core, the shell comprising: A substantially inorganic first shell member, the substantially inorganic first shell member comprising: a condensation layer comprising a condensation product of a precursor, and a nanoparticle layer comprising inorganic nanoparticles, wherein the condensation layer is disposed between the core and the nanoparticle layer, and an inorganic second shell member surrounding the first shell member, wherein the inorganic second shell member surrounds the nanoparticle layer, and wherein the precursor comprises at least one compound of formula (I), (M v O z Y n ) w (Formula I) Wherein M is one or more of silicon, titanium and aluminum, v is the valence number of M and is 3 or 4, z is 0.5 to 1.6, Each Y is independently selected from -OH, -OR 2 , halogenated, -NH2, -NHR 2 、-N(R 2 )2 and Where R 2 For C1 to C 20 Alkyl, C1 to C 20 Alkylene, C6 to C 22 aryl or 5-12 membered heteroaryl containing 1 to 3 ring heteroatoms selected from O, N and S, R 3 H, C1 to C 20 Alkyl, C1 to C 20 Alkylene, C6 to C 22 aryl or 5-12 membered heteroaryl containing 1 to 3 ring heteroatoms selected from O, N and S, n is 0.7 to (v-1), and w is 2 to 2000, wherein the first shell component comprises an organic content of at most 5%, wherein the compound of formula (I) has a polystyrene equivalent weight average molecular weight (Mw) of 200 Da to 60,000 Da, The compound of formula (I) has a molecular weight polydispersity index of 1 to 20, wherein the compound of formula (I) has a degree of branching of 0.05 to 0.
6.
2. The capsule of claim 1, wherein the beneficial agent comprises at least one of: a chromogen, a fragrance composition, a fragrance raw material, a lubricant, a silicone oil, a wax, a hydrocarbon, a higher fatty acid, an essential oil, a lipid, a skin cooling agent, a vitamin, a sunscreen, an antioxidant, a catalyst, a malodor attenuator, an odor control material, a softener, an insect repellent, a colorant, a pigment, a medicament, a medicinal oil, an adhesive, a base agent, a disinfecting cloth and a form control agent, a smoothing agent, a wrinkle control agent, a sanitizing agent, a disinfectant, a microbial control agent, a desiccant, a stain repellent, a detergent, a fabric freshener, a freshness extension agent, a chlorine bleach odor control agent, a dye fixative, a color retention agent, a color restoration / recovery agent, an anti-fading agent, an anti-abrasion agent, an anti-wear agent, a fabric integrity agent, an anti-pilling agent, an anti-foaming agent, an ultraviolet protection agent, a light fade inhibitor, an anti-allergenic agent, a fabric comfort agent, an anti-shrinkage agent, an anti-stretch agent, a stretch recovery agent, a skin care agent, a dye, a phase change material, a fertilizer, a nutrient, and a herbicide.
3. The capsule of claim 1, wherein the oil-based core further comprises a core conditioning agent. The capsule of claim 1 , wherein the shell permeability is between 0.01% and 40%.
5. A capsule, comprising: an aqueous core comprising a benefit agent; and A shell surrounding the core, the shell comprising A substantially inorganic first shell member, the substantially inorganic first shell member comprising: a condensation layer comprising a condensation product of a precursor, and a nanoparticle layer comprising inorganic nanoparticles, wherein the precursor comprises at least one compound of formula (I), (M v O z Y n ) w (Formula I) Wherein M is one or more of silicon, titanium and aluminum, v is the valence number of M and is 3 or 4, z is 0.5 to 1.6, Each Y is independently selected from -OH, -OR 2 , halogenated, -NH2, -NHR 2 、-N(R 2 )2 and Where R 2 For C1 to C 20 Alkyl, C1 to C 20 Alkylene, C6 to C 22 aryl or 5-12 membered heteroaryl containing 1 to 3 ring heteroatoms selected from O, N and S, R 3 H, C1 to C 20 Alkyl, C1 to C 20 Alkylene, C6 to C 22 aryl or 5-12 membered heteroaryl containing 1 to 3 ring heteroatoms selected from O, N and S, n is 0.7 to (v-1), and w is 2 to 2000, and wherein the mass % of the condensed layer relative to the total mass of the shell is 10% to 99%, wherein the first shell component comprises an organic content of at most 5%, wherein the compound of formula (I) has a polystyrene equivalent weight average molecular weight (Mw) of 200 Da to 60,000 Da, The compound of formula (I) has a molecular weight polydispersity index of 1 to 20, wherein the compound of formula (I) has a degree of branching of 0.05 to 0.
6.
6. The capsule of claim 5, wherein the shell further comprises an inorganic second shell member surrounding the first shell member.
7. The capsule of claim 5, wherein the benefit agent comprises at least one of a fragrance raw material, a fragrance composition, a skin cooling agent, a vitamin, a sunscreen, an antioxidant, a glycerin, a bleach encapsulate, a chelating agent, an antistatic agent, an insect repellent, a colorant, an antioxidant, a sanitizer, a disinfectant, a microbial control agent, a desiccant, a stain repellent, a detergent, a chlorine bleach odor control agent, a dye fixative, a dye transfer inhibitor, a color retention agent, an optical brightener, a color restoration / recovery agent, an anti-fading agent, a whiteness enhancer, an anti-abrasion agent, an anti-wear agent, a fabric integrity agent, an anti-pilling agent, an anti-foaming agent, an ultraviolet protection agent, a photofade inhibitor, an anti-allergenic agent, a water repellent, a fabric comfort agent, an anti-shrinkage agent, an anti-stretch agent, a stretch recovery agent, a skin care agent, an antimicrobial active, an antiperspirant active, a cationic polymer, a dye, a metal catalyst, a non-metal catalyst, an activator, a preformed peroxycarboxylic acid, a diacyl peroxide, a source of hydrogen peroxide, or an enzyme.
8. The capsule according to claim 1 or 5, wherein the precursor comprises at least one compound of formula (II), (M v O z Y n R 1 p ) w (Formula II) Wherein M is one or more of silicon, titanium and aluminum, v is the valence number of M and is 3 or 4, z is 0.5 to 1.6, Each Y is independently selected from -OH, -OR 2 , halogenated, -NH2, -NHR 2 、-N(R 2 )2 and, where R 2 For C1 to C 20 Alkyl, C1 to C 20 Alkylene, C6 to C 22 aryl or 5-12 membered heteroaryl containing 1 to 3 ring heteroatoms selected from O, N and S, n is 0 to (v-1), Each R 1 Independently selected from C1 to C 30 Alkyl, C1 to C 30 Alkylene, C1 to C2 substituted by one or more of halogen, -OCF3, -NO2, -CN, -NC, -OH, -OCN, -NCO, alkoxy, epoxy, amino, mercapto, acryloyl, CO2H, CO2 alkyl, aryl and heteroaryl. 30 Alkyl, and C1 to C2 substituted by one or more of halogen, -OCF3, -NO2, -CN, -NC, -OH, -OCN, -NCO, alkoxy, epoxy, amino, mercapto, acryloyl, CO2H, CO2 alkyl, aryl and heteroaryl. 30 Alkylene, p exists in an amount at most pmax, and w is 2 to 2000; Where pmax = 60 / [9*Mw(R 1 )+8], where Mw(R 1 ) is the R 1 The molecular weight of the group.
9. The capsule of claim 1, wherein the inorganic second shell component comprises one or more of SiO2, TiO2, Al2O3, CaCO3, Ca2SiO4, Fe2O3, Fe3O4, iron, silver, nickel, gold, copper, and clay.
10. The capsule according to claim 1 or 5, wherein the inorganic nanoparticles of the first shell member include one or more of metal nanoparticles, mineral nanoparticles, metal oxide nanoparticles, and semi-metal oxide nanoparticles.
11. The capsule according to claim 1 or 5, wherein the inorganic nanoparticles include one or more of SiO2, TiO2, Al2O3, Fe2O3, Fe3O4, CaCO3, clay, silver, gold and copper. 12 . The capsule of claim 1 , wherein the capsule has an average volume-weighted capsule diameter of 0.1 μm to 200 μm.
13. The capsule of claim 1 or 5, wherein the shell has a thickness of 10 nm to 10,000 nm.
14. The capsule according to claim 8, wherein the compound of formula (I) has a polystyrene equivalent weight average molecular weight (Mw) of 400 to 60,000 Da, and the compound of formula (II) has a polystyrene equivalent weight average molecular weight (Mw) of 200 to 60,000 Da. 15 . The capsule of claim 8 , wherein the compound of formula (I) has a molecular weight polydispersity index of 1 to 10, and the compound of formula (II) has a molecular weight polydispersity index of 1 to 20.
16. The capsule according to claim 8, wherein the compound of formula (I) has a branching degree of 0.2 to 0.6, and the compound of formula (II) has a branching degree of 0.05 to 0.
6.
17. The capsule according to claim 8, wherein for formula (I) or formula (II), M is silicon, Y is OR and R is one or more of methyl, ethyl, propyl or butyl.
18. The capsule of claim 1 or 5, wherein the precursor further comprises at least one of TMOS, TEOS or TBOS.
19. The capsule of claim 1 or 5, wherein the capsule has an average nominal wall tension of 0.1 N / m to 50 N / m.
20. The capsule of claim 1 or 5, wherein the volume core / shell ratio is 80:20 to 98:
2.
21. The capsule of claim 1 or 5, wherein the substantially inorganic first shell component comprises at most 2% organic content.
22. The capsule according to claim 2 or 7, wherein the microorganism control agent is a mold control agent, a mildew control agent or an antiviral agent.
Citation Information
Patent Citations
Composition of menthol and menthyl lactate, its preparation method and its applications as a cooling agent
US6897195B2
Capsule comprising active ingredient
WO2011131644A1
Microcapsules comprising active ingredients and metal oxide shell, method for their preparation and uses thereof
CN102112219A
Capsule comprising active ingredient
CN102858449A
Method for producing a capsule comprising a liquid active substance core surrounded by an inorganic shell
JP2002528259A